Co@C nanoparticles supported on interparticle porosity-dominated MFI zeolites with adjustable surface Lewis acidity for efficient and selective styrene hydroformylation - Sirui Wu; Hongchun Sun; Meihui Yu; Xiaoying Zhang; Yuting Qi; Yukun Shi; Xin Shi (Fuel, 2027)

Glucose dose-dependently modulates antimicrobial peptide genes expression through the ERK/PI3K-NF-κB/FOXO signaling in Chinese mitten crab (Eriocheir sinensis) - Jinming Yu; Sixuan Li; Yuting Xi; Yiyang Xu; Chang Liu; Yuhan Tu; Siyue Li; Junwei Guo; Haidong Zou; Jinming Yuan; Yuhan Ma; Dazuo Yang; et al. (Fish & Shellfish Immunology, 2026)

Scalable nanoconfined GO/SWCNT-OH membranes for efficient high-salinity organic wastewater treatment - Yechen An; Xiaoxu Gao; Jing-Long Han; Yuting Ning; Xinping Fu; Ruiyun Ren; Liang Mei; Wenli Jiang; Ruifeng Yan; Jun Cui; Yu Tao; Aijie Wang (Water Research, 2026)

Balancing dietary intake targets and outsourced burdens in China's food system: A scenario-based framework for sustainable consumption and production - Ying Xu; Xiaowei Chuai; Xiaoxi Yu; Shuai Li; Tong Wang; Yuting Luo (Sustainable Production and Consumption, 2026)

Structural and functional characterization of whey protein isolate-polyphenol covalent conjugates prepared via electrochemical oxidation, alkaline treatment, and free radical grafting - Jinshun Ye; Ying Xu; Yuting Li; Wenxue Cheng; Xiaozhen Liu; Xiangying Yu; Jingkun Yan; Lin Li (Food Research International, 2026)

Vortex bionic structural composites fabricated by DLP 3D printing with high electromagnetic shielding effect and thermal conductive property - Jingxing Gui; Tao Zhang; Sha Long; Yingtao Li; Feiyue Zhou; Yuxuan Ma; Yuting Xue; Xueting Xu; Chunyan Hu; Baojiang Liu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Breaking biofilm barriers and reprogramming immunity: NIR-activated protease–copper nanozymes drive cuproptosis-like killing and accelerate infected wound repair - Yi Hu; Zijian Hu; Yuting Ding; Yuan Zhou; Duo Zhou; Song Ye; Wei Jiang; Yanbin Zhang; Junhui Song; Chengying Meng; Yu Chen; Yueyang Fang; et al. (Chemical Engineering Journal, 2026)

Self-adhesive small intestinal submucosa-based hydrogel patch with dual-stage sequential curcumin release for pulmonary air leak sealing, sustained anti-inflammatory modulation, and lung regeneration - Yuting Cheng; Daping Yu; Zixun Wang; Bo Zhao; Pengfei Wei; Wei Jing; Yiqian Huang; Yuxin Guo; Huimin Li; Xuening Wang; Peng Jiao; Yandong Li; et al. (Chemical Engineering Journal, 2026)

Rapid Detection of Spring Viremia of Carp Virus ( SVCV ) Using RAA ‐ CRISPR /Cas12a - Xiaoyang Li; Aoqing Zhang; Yingying Li; Yingying Wang; Hao Zheng; Defeng Zhang; Yan Ren; Xubing Mo; Yuting Deng; Junyu Luo; Meiling Yu; Bo Chen; et al. (Journal of Fish Diseases, 2026)
Spring viremia of carp virus (SVCV), that can infect cyprinoid and koi causing an acute hemorrhagic symptom, with a feature of widespread epidemic, which poses a severe threat to the global aquaculture industry. Given the absence of specific effective medicine or vaccines, the early, accurate diagnosis is critical in the disease prevention. Many SVCV detection methods have been established, but most require specialized equipment and skilled operators, which limits their field application. In this study, we established a recombinase‐mediated isothermal amplification (RAA) in conjunction with the CRISPR/Cas12a system targeting the screened conserved region of the G gene in the genome to identify SVCV. The optimal combination of the primer pairs and crRNA was screened via the fluorescence intensity. In addition, the test exhibited high sensitivity and specificity, which could detect at the limit of 1.243 × 10 1 copies/μL and show no cross‐reactivity with other common freshwater fish pathogens. Furthermore, the result could be visible by excitation of fluorophores by blue light at 39°C within 30 min. The integrated method combines the advantages of RAA and CRISPR‐based signal transduction, offering a diagnosis project in resource‐limited aquaculture environments and a field‐applicable early warning of SVCV.

HIF-1α-Associated Macrophage Metabolic Reprogramming Mediates Intestinal Injury Induced by Acrylamide and 5-Hydroxymethylfurfural Co-exposure - Jiawen Lu; Yangchun Shen; Xingtao Zhou; Yuting Wang; Hui Ye; Qiang Yu; Jianhua Xie; Yi Chen (Journal of Hazardous Materials, 2026)

Corrigendum to “Metabolomics combined with machine learning reveals candidate metabolites and a putative working network associated with cereulide production in emetic Bacillus cereus” [Food Res. Int. 239 (2026) 119523] - Ying Feng; Minling Chen; Jiaxun Li; Keyuan Qin; Moutong Chen; Juan Wang; Qingping Wu; Yuting Shang; Yu Ding (Food Research International, 2026)

Metabolomics combined with machine learning reveals candidate metabolites and a putative working network associated with cereulide production in emetic Bacillus cereus - Ying Feng; Minling Chen; Jiaxun Li; Keyuan Qin; Moutong Chen; Juan Wang; Qingping Wu; Yuting Shang; Yu Ding (Food Research International, 2026)

Transitions from polyphenol and phytosterol to oil accumulation in developing Camellia seeds - Tuo Leng; Yuting Wang; Xiaoyi Hu; Qiang Yu; Yi Chen (Food Chemistry, 2026)

Mitigation role of edible oil and polyol sweeteners in the formation of acrylamide and 5-hydroxymethylfurfural in baked bread - You Long; Feng Li; Yuting Wang; Qiang Yu; Jianhua Xie; Yi Chen (Food Control, 2026)

Zearalenone-induced hepatotoxicity: Underlying mechanisms and genistein-mediated preventive effects - Ruo Du; Qingyuan Li; Yi Cheng; Yuting Zeng; Mairewulan Abula; Wenyi Liu; Fangfang Yu; Weihua Jia; Yuhui Du; Yue Ba; Yanjie Wang; Guoyu Zhou (Food and Chemical Toxicology, 2026)

A fluorescent/photochromic dual-function Mo-based hydrogel for information encryption - Sha Long; Yanghang Liu; Jingxing Gui; Yuting Xue; Yuxuan Ma; Baojiang Liu; Chunyan Hu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Supported catalytic packing by epoxy resin porous transition layer on stainless steel for reactive distillation of ethyl acetate - Haoran Yin; Miao Yu; Yuting Wu; Mingyu Yu; Yong Sha (Chemical Engineering Journal, 2026)

Disruption of intestinal mucosal immunity and microbial homeostasis in Schizothorax davidi under chronic DBP exposure: From functional compensation to transcriptional decompensation - Luo Lei; Rongrong Liao; Mei Peng; Yinhua Zhou; Chang Xiao; Xiayu Yu; Shuang Liu; Yuting Duan; Suxing Fu; Hejiao Li; Can Liu; Xiao Chen; et al. (Aquatic Toxicology, 2026)

Synergistic effects of co-pyrolyzed rice straw/non-woven fabric biochar on soil enhancement and rice growth promotion - Shuo Su; Jiachen Zhu; Tian Xie; Zhihua Zhang; Yi Zhu; Yu Xie; Yuting Ran; Lingling Yao; Jie Qin; Jing Huang; Junxin Zhou; Zhi Zhou; et al. (Paddy and Water Environment, 2026)

Experimental investigation into the solidification effect of nano-TiO 2 regulated microbially-induced calcium carbonate precipitation - Yuxuan Zhou; Jun Hu; Xiaoqing Yuan; Yu Du; Yuhui Wu; Yuting Chen (Marine Georesources & Geotechnology, 2026)

Covalent organic frameworks for food contaminant detection: Applications and DFT calculations - You Long; Yuting Wang; Gan Zhang; Yichun Wang; Qiang Yu; Yi Chen (Trends in Food Science & Technology, 2026)

Retraction notice to “Influence of the morphological change in natural Asian dust during transport: A modeling study for a typical dust event over northern China” [Sci. Total Environ. 739 (2020) 139791] - Yu Tian; Zhe Wang; Xiaole Pan; Jie Li; Ting Yang; Dawei Wang; Xiaoyong Liu; Hang Liu; Yuting Zhang; Shandong Lei; Yele Sun; Pingqing Fu; et al. (Science of The Total Environment, 2026)

Large band curvature in semimetal-semiconductor NbSe2/WSe2 heterojunctions for high-speed imaging - Yan Zhou; Wei Shangguan; Huihui Yu; Haoran Zeng; Yuting Xu; Junli Du; Xiankun Zhang; Zheng Zhang; Yue Zhang (Science Bulletin, 2026)

Enhancing large-scale streamflow prediction by coupling structural inductive bias with meta-learning - Xuan Tang; Yuting Zhao; Yuan Yu; MingRui Yu; Guanghua Qin; Hongxia Li (Journal of Hydrology, 2026)

A novel Camellia oil microemulsion significantly enhances the bioaccessibility and antioxidant activity of curcumin: a comparative study with macroemulsion - Jingyi Chen; Jiayi Zou; Yuting Yang; Wei Li; Qihui Shui; Man Tian; Yu Zhou; Xingfa Han; Tao Chen; Lijun Zhou (Food Chemistry, 2026)

Progress in the simultaneous detection of multiple targets in food safety using programmable nucleases - Xiang Gao; Qi Chen; Qingping Wu; Yuting Shang; Yu Ding (Current Opinion in Food Science, 2026)

Multifunctional BQD interlayer enables high-resolution high-efficiency QLEDs:Eliminating EML void defects and optimizing interfacial carrier transport - Yue Chen; Yuting Bai; Zunxian Yang; Luxi Yuan; Ye Chen; Xudong Jiang; Jiajie Hong; Benfang Liu; Zhiyu Yuan; Jinzhu Gao; Zhezhou Fang; Runsen Yu; et al. (Chemical Engineering Journal, 2026)

Association between venetoclax concentration and febrile neutropenia in acute leukemia: a retrospective analysis - Yuting Yan; Jin Sun; Yujiao Guo; Jieyu Sun; Yu Zhu; Luning Sun; Yongqing Wang (European Journal of Clinical Pharmacology, 2026)

Synthesis and preliminary anticancer evaluation of thiazole derivatives of diphyllin - Yuting Zhang; Jun Zhang; Siwei Ji; Zhijiao Yan; Jun Xu; Yu Zhao (Natural Product Research, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Anti-rheumatoid arthritis sesquiterpenoids from the roots of Lindera glauca - Siqi Li; Jiacheng Weng; Gang Li; Zheyuan Lin; Yu Zhou; Yuting Wu; Xiongyu Meng; Qi Shi; Guifen Zhou; Luping Qin; Huaqiang Li (Phytochemistry, 2026)

AI-driven monitoring strategy optimization for nutrient-polluted groundwater in a desert site in Northwest China - Yuting Yan; Yu Liu; Baocai Tong; Jinsheng Wang; Rui Zuo; Yuyu Wan; Yuanzheng Zhai; Xu Han (Journal of Hydrology, 2026)

Low-dose PFOS exposure exacerbates rheumatoid arthritis via SIRT2–PAD4–mediated macrophage pyroptosis - Zeqing Sun; Linghui Yu; Yun Li; Haoran Guo; Mengyao Li; Yuting Wen; Shasha Yao; Qiuju Liang; Zhijie Xu; Jiaqi Zhang; Ming Yang; Sijin Liu; et al. (Journal of Hazardous Materials, 2026)

Artemisinin derivative SM934 targets α-enolase to inhibit PEP-mediated TAK1 stabilization and inflammation - Jun Pan; Yuwei Zhang; Zhiwei Du; Yuanyuan Huang; Yu Wang; Miya Su; Yuting Cai; Weiya Xu; Lili Chen; Chengdong Huang; Di Cui; Dongsheng Chen; et al. (Science China Life Sciences, 2026)

Resource‐Dependent Metabolic and Biogeochemical Consequences of Viruses in Agricultural Soils - Guixiang Zhou; Junxi Liu; Fangming Liu; Yu Xiao; Emily B. Graham; Yakov Kuzyakov; Mao Ye; Xiuli Xin; Lin Chen; Congzhi Zhang; Donghao Ma; Zongzhi Wu; et al. (Global Change Biology, 2026)
Soil viruses are crucial for microbial life, biogeochemical cycles of carbon and nutrients, and for microbial necromass formation. We hypothesized that the effects of viruses on these processes depend on organic matter and nutrient availability in soils. Here, we combined a 34‐year long‐term fertilization trial, 150 sequenced soil metagenomes, and microcosm experiments to explore how viruses modulate carbon and nutrient dynamics depending on resource availability. We uncovered 2789 viral populations (vOTUs) grouping into 301 viral clusters, 91% of which were previously unknown. Organically fertilized soils harbored most lytic viruses carrying diverse element cycling‐related auxiliary viral genes (AVGs) acquired through co‐evolution and horizontal gene transfer. Synthesis and heterologous expression assays further indicated that four AVGs (i.e., cbhA , pel , wbpD , GT2 ) had higher transcript levels in Escherichia coli under nutrient rich than nutrient poor conditions. Addition of virus particles to soils raised microbial carbon use efficiency (CUE; biomass production relative to carbon uptake) and accelerated microbial turnover leading to boosted microbial necromass formation by 14%. Conversely, in soils without organic fertilizers, viruses facilitate bacterial adaptation to stress (e.g., defense system and interference competition) and accelerate microbial decomposition of organic matter. 35 days after virus addition, CO 2 and N 2 O emissions increased by 41% and 52%, respectively. Finally, we propose the Viral Entombing‐Priming (VEP) framework to describe the contrasting roles of viruses in carbon and nutrient dynamics depending on soil fertility. This work reveals the viral “Matthew effect” ( the rich get richer and the poor get poorer ) in resource‐rich and resource‐poor soils and could unlock nature‐based pathways to raise carbon and nutrient retention for sustainable agriculture.

Species-specific salinity adaptation mechanisms drive niche partitioning of nitrite-dependent anaerobic methane oxidation bacteria in a natural wetland gradient - Zixuan Ren; Yuting Wen; Yushan Ma; Minghui Li; Lixin Wang; Ruihong Yu; Linhui Wu (Water Research, 2026)

Cracking characteristics of rock-anchored beam system during construction of underground powerhouse under high in-situ stress and complex rock mass structures: A case study of Yebatan hydropower station - Peiyang Yu; Xiuli Ding; Shuling Huang; Xinhao Zhu; Yang Qin; Jianhua He; Yuting Zhang; Gang Han (Tunnelling and Underground Space Technology, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Three-dimensional morphodynamic modeling of reef islands with varying geomorphic and sedimentary characteristics - Yu Yao; Chengyu Liu; Shengnan Zhou; Yuting Song (Marine Geology, 2026)

Unraveling structure-driven astringency perception of polyphenols and elucidating multimodal mitigation mechanism by citrus pectin - Haiwa Wang; Kaichang Zhao; David Julian McClements; Yi Chen; Qiang Yu; Taotao Dai; Yuting Wang (Food Bioscience, 2026)

Directed evolution of a miniature Cas12f1 nuclease from Acidibacillus sulfuroxidans for expanded PAM recognition and enhanced nuclease activity - Zhengqun Li; Yuting Deng; Yanan Huo; Ting Nie; Siyuan Wang; Dali Li; Guang-Yu Yang (Chemical Engineering Journal, 2026)

A lightweight two-stage framework for headland navigation area localization and path extraction in cornfields - Yuting Zhai; Jian Li; Xiuling Yu; Yang Zhou; Yanlei Xu (Precision Agriculture, 2026)

Prediction of clock bias for BeiDou satellites using a combination of variational mode decomposition and long short-term memory network - Wenlong Sun; Fengfeng Shi; Yuting Lin; Jinfeng Xu; Guojun Li; Guocheng Wang; Shaofeng He; Jiawei Yu; Pei Ma (Journal of Geodesy, 2026)

Metatranscriptomic discovery of a novel viral class from the Yangshan deep-water port virosphere - Yuting Xie; Shuang Wu; Chen Hu; Hao Yu; Lanming Chen; Yongxin Yu; Yongjie Wang (Archives of Virology, 2026)

Deformation Characteristics of Surrounding Rock in a Large Underground Opening Under High In Situ Stress and Complex Rock Mass Structures: A Case Study of Yebatan Hydropower Station - Peiyang Yu; Xiuli Ding; Shuling Huang; Peng-Zhi Pan; Yuting Zhang; Jianhua He; Ju He; Gang Han (Rock Mechanics and Rock Engineering, 2026)

A stimulating effect induced by Bisphenol A bis (diphenylphosphate) in HepG2 cells via vascular endothelial growth factor (VEGF)/VEGF receptor axis - Jing An; Yuting Yi; Na Li; Miao Lin; Yufang Zhong; Guofa Ren; Yu Shang (Toxicology Letters, 2026)

Overexpression of the Cry1Ac in two poplar species can effectively inhibit Hyphantria cunea - Yuting Wang; Ruiqi Wang; Yu Zhang; Xinyue Wu; Kainat; Boru Zhou; Tingbo Jiang (Pesticide Biochemistry and Physiology, 2026)

Thermal generation of acrylamide, 5-HMF, and AGEs in roasted cashews: Correlation with aroma-active volatiles and quality evaluation - Yuwei Liu; Yilun Huang; Huiyu Hu; Yi Chen; Chang Li; Qiang Yu; Yuting Wang (Food Chemistry, 2026)

Per- and polyfluoroalkyl substances in the environment and human tissue: A critical review of distribution, exposure pathways, and health risks - Zhenyu Zhang; Yuting Liu; Yi Chen; Han Qu; Jiaxue Ma; Mingyue Pang; Bin Wang; Gang Yu (Environmental Pollution, 2026)

Impacts of persistent underground coal fires on radial growth of Picea schrenkiana on the northern slope of the Tianshan Mountains - Tongwen Zhang; Dong Guo; Jinghui Song; Shulong Yu; Shengxia Jiang; Kailong Guo; Tianhao Hou; Xiaoxia Gou; Ruxianguli· Abudoureheman; Huaming Shang; Yuting Fan (Dendrochronologia, 2026)

A smart hydrogel with skin-temperature-triggered adhesion and low-temperature painless detachment for ECG monitoring - Zixuan Lian; Lizhi Wang; Yuting Xue; Yu Jiang; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Ionic liquid tailored poly(ethylene glycol) acylurea networks enabling thermo switchable crystallinity for recyclable iontronic sensing and thermally programmed actuation - Yu Zhang; Yuting Jiang; Yunsheng Xu; Pengwu Xu; Wenjun Peng; Weijun Yang; Shuangfei Xiang; Xianming Zhang (Chemical Engineering Journal, 2026)

Nanoscale insights into cellulose–imidazolium ionic liquid interactions via atomic force microscopy - Ruimei Cao; Hongshuai Gao; Wanxue Lv; Yuting Song; Yan Long; Min Yu; Baozeng Ren; Yi Nie; Suojiang Zhang (Carbohydrate Polymers, 2026)

Three-dimensional identification and assessment of compound droughts from a propagation perspective - Zengkun Guo; Yang Yu; Lingxiao Sun; Chunlan Li; Jing He; Mingjie Chen; Yuting Gao; Ireneusz Malik; Malgorzata Wistuba; Ruide Yu (CATENA, 2026)

Light-at-night exposure drives myopia via melanopsin signalling - Jiaxin Li; Congying Li; Meijun Wang; Jianjun Meng; Jiajia Dang; Ying Huang; Di Shi; Xinyu Li; Shan Cai; Tianli Peng; Yunfei Liu; Yuting Kang; et al. (Science China Life Sciences, 2026)

Remote sensing image enhancement and water eutrophication prediction based on atmospheric-water multimodal information fusion - Li Wang; Yihan Sun; Xiaoyi Wang; Jiping Xu; Zhiyao Zhao; Jiabin Yu; Huiyan Zhang; Qian Sun; Yuting Bai (Earth Science Informatics, 2026)

Shifting Biological Drivers Govern Drought and Wetting Legacies on Soil Respiration - Yanan Cui; Stefano Manzoni; Zhiyuan Quan; Daiqi Zhao; Lina Yan; Chengliang Wang; Jidong Liao; Jiancheng Yu; Yuting Liu; Yanan Li; Wei Sun; Baoku Shi (Global Change Biology, 2026)
Climate change is intensifying precipitation extremes, yet how historical drought and wetting shape post‐event soil carbon fluxes remains poorly understood. Using a seven‐year precipitation manipulation experiment (−70% to +50%) followed by a two‐year recovery period in a semi‐arid grassland, we quantified legacy effects on soil respiration (Rs) and its autotrophic (Ra) and heterotrophic (Rh) components. Historical moderate wetting (+30%) generated the strongest positive legacy, increasing Rs, Rh, and Ra by 21.9%, 24.4%, and 26.9%, respectively, during the first recovery year. In contrast, historical drought treatments (−70% to −30%) produced biphasic legacies, characterized by early‐season suppression followed by later‐season positive responses, potentially associated with decomposition of drought‐accumulated substrates and vegetation recovery. Ra generally showed stronger recovery responses than Rh, indicating contrasting sensitivities of plant‐ and microbially ‐ derived respiration to moisture and carbon availability. The dominant controls of respiration also shifted over time: first‐year legacies were associated mainly with microbial carbon substrates and extracellular enzyme activities, whereas second‐year responses were increasingly linked to plant allocation strategy and microbial community composition. Despite these contrasting trajectories, Rs, Ra, and Rh largely converged to control levels within two years. Our results demonstrate that precipitation legacies in semi‐arid grasslands are asymmetric and temporally dynamic, with important implications for predicting carbon cycling under increasing hydrological variability.

Flow regime specific regulation shapes microbial-mediated nitrogen cycling of plain tidal river network - Jiaxin Tong; Wenlong Zhang; Feng Yu; Ruoyu Liu; Yuting Yan; Yi Li (Water Research, 2026)

Alpha-lipoic acid improves intestinal homeostasis and ameliorates colitis through modulation of gut microbiota and production of short chain fatty acids in mice - Shouhe Huang; Huafang Ding; Yuting Su; Zixing Chen; Wensen He; Zhen-Yu Chen; Hanyue Zhu (Food Research International, 2026)

Breaking symmetry of active sites to enable long-lived shallow trapping in COFs for photocatalytic remediation of uranium-contaminated wastewater - Weijie Zhang; Xinxu Deng; Yuting Zhu; Hai Yang; Fengtao Yu; Chengshuai Liu (Chemical Engineering Journal, 2026)

Technologies of Construction and Management for Sustainable Utilization of Riverbank Filtration - Yuanzheng Zhai; Yuting Yan; Yu Liu; Yizhai Ma; Baocai Tong; Rui Zuo (Journal of Earth Science, 2026)

How keystone taxa shape sediment carbon accumulation during lake restoration: A new insight from asynchronous regime shifts of community structure and function - Feng Yu; Wenlong Zhang; Zikang Tang; Yajie Zhu; Yuting Yan; Yi Li (Water Research, 2026)

Widely targeted metabolomics reveals chemical mechanism of bloating in Rosa roxburghii Tratt juice induced by vitamin C and its chiral isomers - Hong Yang; Yuting Liu; Xinying Wang; Wenxin Zhang; Bo Peng; Dalong Chen; Angze Gao; Weixin Huang; Pin Qian; Deshun Yu; Yifu Tian; Xianzhi Dong (Food Chemistry, 2026)

Development of a novel soybean protein isolate - rice bran wax bigel system: Effects of alternating electric field pretreatment and hydrogel/oleogel ratio on bigel properties - Yuting Wang; Ning Wang; Heqing Yang; Tong Wang; Cuiping Han; Dianyu Yu (Food Hydrocolloids, 2026)

Optoelectronic synaptic transistor array based on CsPbBr3/grating-patterned IDTBT heterojunctions for neuromorphic visual fatigue sensing - Jiajie Hong; Zhiqian Wei; Zunxian Yang; Yue Chen; Luxi Yuan; Shangwei Ye; Xudong Jiang; Yuting Bai; Benfang Liu; Zhiyu Yuan; Wenxin Zhang; Jie Li; et al. (Chemical Engineering Journal, 2026)

TEDD 2.0: an advanced temporal gene expression database enabled by in-silico functional analyses for developmental mechanism investigation - Chi Chun Chan; King Kin Lam; Lin Chen; Mingyang Yu; Jingwen Hu; Yujie Zhu; Yuting Zheng; Jia Zheng; Kwong Wai Choy; Zirui Dong (Science China Life Sciences, 2026)

Thioether and ether derivatives of diphyllin: synthesis and inducing tumor ferroptosis activity - Jianhang Han; Yujie Ma; Siwei Ji; Fan Yang; Qinyao Lu; Yuting Zhang; Yu Zhao (Natural Product Research, 2026)

Disentangling phytoplankton regime shifts and ecosystem stability under water diversion: Insights from functional traits and trophic interactions in a mesocosm experiment - Yajie Zhu; Wenlong Zhang; Feng Yu; Zikang Tang; Yuting Yan; Ruoyu Liu; Jiaxin Tong; Yi Li (Water Research, 2026)

Enhanced removal of anionic Per- and polyfluoroalkyl substances (PFAS) by electrically assisted nanofiltration: Operational parameter optimization and mechanistic insights - YuTing Hua; Yu Li; Peng-Fei Li; BeiBei Chai; ZhiXuan Zhou; JingYi Wu (Journal of Hazardous Materials, 2026)

3D-printed fish-scale dam-like structured photothermal evaporators based on thiol-ene click chemistry for solar-driven freshwater production and salt recovery - Lixuan Yang; Xiaoyu Fu; Zhihan Xu; Feiyue Zhou; Jingxing Gui; Yuting Xue; Yuxuan Ma; Dan Yu; Wei Wang (Journal of Cleaner Production, 2026)

Hydrogenophaga-bioaugmented microalgal-bacterial granular sludge for efficient treatment of chloramphenicol-containing wastewater - Shengjie Xiang; Yang Bai; Min Yu; Hassimi Abu Hasan; Yuting Shi; Can Tong; Yuan Tian; Anjie Li; Bin Ji (Journal of Environmental Chemical Engineering, 2026)

Cysteine synthesis pathway-mediated biological removal of H₂S in PDMS-SiO₂ modified membrane bioreactors - Yu Xiao; Yuting Li; Yongxu Jin; Qiubi He; Yalan Shi; Yingzhou Huang; Shijie Wang; Xiang Wang (Chemical Engineering Journal, 2026)

Comammox ammonia oxidization and N2O production in vadose and saturated zone soils - Shanyun Wang; Ruiliang Xu; Manyi Xiao; Jie Yu; Longbin Yu; Zihao Heng; Zhiyuan Li; Qingbang Du; Yuting Zhou; Yifei Li; Guibing Zhu (Water Research, 2026)

AP2-domain transcription factor WRI5a-regulated MtABCB1 promotes arbuscule development in mycorrhizal symbiosis - Wanxiao Wang; Yuting Wang; Qiujin Xie; Jincai Shi; Linfeng Sun; Zuhua He; Jeremy Murray; Ertao Wang; Nan Yu; Xiaowei Zhang (Science Bulletin, 2026)

Impact of indole and its derivatives in the environment: Metabolic mechanisms, functional properties, and ecological effects - Yijie Wang; Yu Hua; Shuxian Chen; Hong Wang; Yan Li; Chong Chen; Yuting Zhu; Yue Zhang; Xiaohu Dai (Journal of Environmental Management, 2026)

A dissolved oxygen prediction model integrating ChatGPT expert knowledge-driven attention mechanism and normalization - Xiangfeng Bu; Li Wang; Xiaoyi Wang; Jiping Xu; Zhiyao Zhao; Jiabin Yu; Huiyan Zhang; Qian Sun; Yuting Bai (Journal of Contaminant Hydrology, 2026)

Metabolomic insights into the role of isoleucine in regulating cereulide biosynthesis in emetic Bacillus cereus - Jiaxun Li; Keyuan Qin; Yuting Shang; Zhenjun Zhu; Yangfu Li; Junhui Wu; Moutong Chen; Liang Xue; Qingping Wu; Juan Wang; Yu Ding (Food Research International, 2026)

Magnetic covalent organic framework with theory calculation coupled to UPLC-MS/MS for selective enrichment and simultaneous quantification of seven emerging mycotoxins in wheat - You Long; Yuting Wang; Gan Zhang; Bei Gan; Qiang Yu; Jianhua Xie; Xinyi Zang; Yi Chen (Food Chemistry, 2026)

Flavor modulation of braised He Bao carp (Cyprinus carpio) by natural plant spices: Insights from GC–MS, GC–IMS, E-nose, E-tongue, and molecular docking analyses - Yuwei Liu; Yuting Wang; Ziyi Liu; Chang Li; Qiang Yu; Jianhua Xie; You Long; Qianzhu E; Yi Chen (Food Bioscience, 2026)

Upcycling waste monoacid into functionalized silica for starch-coated paper with enhanced water resistance, barrier properties, and strength via a green process - Yuting Ma; Ruihao Zhang; Meisi Chen; Min Yu; Wen Sun; Zekai Jin; Tao Ma; Begjanova Goze; Haijun Xu; Xinbao Zhu (Chemical Engineering Journal, 2026)

Dendrisome-enabled discrete high-density gold nanocluster assemblies for rapid microfluidic detection of Vibrio parahaemolyticus via magnetic sandwich dynamic capture - Guoyang Chen; Yanyan Shang; Xianhu Wei; Jiaqi Zhao; Xinran Xiang; Jingjing Zou; Yuting Shang; Yanmei Feng; Jumei Zhang; Qinghua Ye; Yu Ding; Youxiong Zhang; et al. (Chemical Engineering Journal, 2026)

Spatial preemption-based mechanisms explain aboveground biomass of Potentilla bifurca in response to nitrogen addition in a temperate grassland community - Liuyi Yang; Huiqiu Shi; Lulu Zhang; Yuting Li; Liang Gao; Qiang Yu; Changliang Shao; Honghui Wu; Wen-Hao Zhang (Plant and Soil, 2026)

The impaired hemodynamics of choroid plexus and its interactions within the glymphatic system in Parkinson’s disease - Song’an Shang; Shaohua Ding; Yuting Xia; Hongying Zhang; Xiang Lv; Beilei Chen; Daming Shen; Jing Ye; Yu-Chen Chen (GeroScience, 2025)

Transforming glyphosate mother liquor into zirconium‑phosphorus composite adsorbent for effective Pb (II) removal from lead‑zinc tailing leachate - Bowen Dong; Ruipu Wang; Shuang Xi; Yuanping Guo; Jing Wang; Yuting Li; Li Guo; Yuchi Chen; Ruan Chi; Jia Wang; Junxia Yu (Journal of Water Process Engineering, 2025)

Regulating electronegativity difference and piezoelectric strain of the Mo-S-Mo structure via introducing S vacancies for boosting piezo-photoelectric activity - Yanjiao Li; Yuting Ning; Xinping Fu; Yu Jiang; Lianfeng Wang; Jun Cui (Journal of Environmental Chemical Engineering, 2025)

Community interactions drive phytoplankton regime shifts in interconnected water bodies: Insights from space for time approach - Yajie Zhu; Wenlong Zhang; Yasong Chen; Feng Yu; Zikang Tang; Zexin Li; Yuting Yan (Journal of Environmental Management, 2025)

Citric acid modification of insoluble dietary fiber from soybean residue: Microstructural reconstruction, interfacial activity enhancement and stability by pickering emulsions - Ziyue Yu; Yuting Yang; Ying Zhang; Ruining Zhang; Bo Lyu; Sainan Wang; Wendan Jing; Hansong Yu (Food Research International, 2025)

Preparation of sodium alginate/sodium carboxymethyl cellulose composite coating film and evaluation of its effects on mango preservation - Wei Wang; Jiakai Yu; Yuting Huang; Bai-Jun Li; Wenzhu Shen; Wenli Zhang; Yining Xia; Qiong Lin (Food Chemistry, 2025)

Effects of botanical-geographical origin and storage time on the composition of free and bound polymethoxyflavones in dried citrus peels - Difan Li; Xiangying Yu; Qiuxia Wei; Zexi Yin; Yahui Yu; Yuting Li; Jingkun Yan (Food Chemistry, 2025)

Ellagic acid protects against intestinal injury induced by acrylamide combined with 3-chloro-1,2-propanediol via the Wnt/β-catenin pathway - Ziyan Guo; Yuting Wang; Shiyu Chen; Ruihong Dong; Qiang Yu; Jianhua Xie; Doris Marko; Yi Chen (Food Bioscience, 2025)

Atomic-scale regulation of Bi2Te3 nanopores via in-situ electron beam irradiation for nanofabrication - Yuting Shen; Yu Tao; Tao Xu; Yuwei Xiong; Kuibo Yin; Yilong Zhou; Shan Cong; Litao Sun (Chemical Engineering Journal, 2025)

Serum metabolomic analysis in mice exposed to perfluorooctanoic acid and sodium p-perfluorous nonenoxybenzene sulfonate - Yuting Xu; Ruochen Ren; Minjie Yu; Wentong Zheng; Yang Wen; Zhen Wang; Hongbo Zeng (Molecular & Cellular Toxicology, 2025)

Cover Image - Yuting Fu; Can Mao; Jianfei Wan; Qianqian Sun; Fangzhao Yu; Jie Sun; Jiang Wu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)

Detection and Genomic Characterisation of Scale Drop Disease Virus (SDDV) in Farmed Yellowfin Seabream ( Acanthopagrus latus ) in Southern China - Yuting Fu; Can Mao; Jianfei Wan; Qianqian Sun; Fangzhao Yu; Jie Sun; Jiang Wu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)
Scale drop disease virus (SDDV) is a distinct member of the genus Megalocytivirus within the family Iridoviridae , which was recently identified as a causative agent of yellowfin seabream Acanthopagrus latus ascitic diseases (YFSBAD). Here, a molecular surveillance of SDDV in pond‐cultured yellowfin seabream was conducted during 2021 to 2023 in Zhuhai, the most significant breeding region for this fish species in China. A total of 73 batches of naturally diseased yellowfin seabream samples were collected for SDDV detection. As a result, 31 samples were confirmed SDDV positive by conventional PCR detection, among which 9 additional SDDVs were isolated by using MFF‐1 cell line, and 4 isolates were further validated by monoclonal antibody‐based immunofluorescence assays. Multiple alignment and phylogenetic analysis revealed that these isolates shared the identical mcp sequences and were clustered within the same clade. Additionally, the complete genome sequence of a new SDDV isolate (SDDV‐ZH918/23) was determined and annotated. The result shows that SDDV‐ZH918/23 consists of 131,741 bp and encodes 143 putative open reading frames. The genome collinearity analysis demonstrated very high nucleotide similarity among all SDDV isolates distributed in China and other Asian countries. Unexpectedly, a 152 bp deletion mutant was also found in two SDDV isolates. Collectively, our study once again demonstrates that SDDV acts as an emerging etiological agent in farmed yellowfin seabream, and a partial deletion mutant of the SDDV genome was first recorded.

The fungicide jinggangmycin stimulates fecundity of Nilaparvata lugens Stål via ILP/Foxo signaling - Xudong Zhao; Yuting Ding; Zhirou Duan; Di Deng; Zhiyue Mao; Yan Zhu; Xiaoxi Fan; Guohui Yu; Linquan Ge (Pesticide Biochemistry and Physiology, 2025)

Dynamics of a pine wilt disease control model with nonlocal competition and memory diffusion - Yuting Ding; Pei Yu (Mathematical Biosciences, 2025)

Using urban-suburban difference of atmospheric CO2 to evaluate carbon neutrality capacity in Hangzhou, China - Bing Qi; Cheng Hu; Yan Yu; Yuting Pang; Fangqi Wu; Xinjie Yang; Huili Liu; Junqing Zhang; Qitao Xiao; Cheng Liu; Wei Xiao (Journal of Environmental Sciences, 2025)

Determining the differences in O3-NOx-VOCs sensitivity between sauna and roast days - Yuting Liu; Yinghong Wang; Yusi Liu; Mengtian Cheng; Baoxian Liu; Tao Song; Bo Hu; Dan Yao; Miao Yu; Yu Shi; Guiqian Tang; Yuesi Wang (Journal of Environmental Sciences, 2025)

Corrigendum to “Folate content and stability in commercial beers: Correlations with phenolic compounds” [Food Chem. 439 (2025) 145828] - Jinxian Zheng; Weiming Huang; Yuting Li; Xiaozhen Liu; Xiangying Yu; Longqing Li; Mingyu Jin; Jing-Kun Yan; Fengyuan Liu (Food Chemistry, 2025)

Folate content and stability in commercial beers: Correlations with phenolic compounds - Jinxian Zheng; Weiming Huang; Yuting Li; Xiaozhen Liu; Xiangying Yu; Longqing Li; Mingyu Jin; Jing-Kun Yan; Fengyuan Liu (Food Chemistry, 2025)

Effect of quinone concentration and pH on the structural and functional properties of bovine serum albumin-chlorogenic acid quinone covalent conjugates - Jinshun Ye; Jinqu Wen; Zhenzhao Weng; Yuting Li; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Jingkun Yan; Lin Li (Food Chemistry, 2025)

Anthocyanin-sulfated polysaccharide–ovalbumin nanocomplex: Intestinal absorption mechanism and intracellular antioxidant activity in Caco-2 cells - Ruihong Dong; Yuting Wang; David Julian McClements; Qiang Yu; Jianhua Xie; Huijie Zhang; Lizhi Huang; Bin Li; Jinlong Tian; Yi Chen (Food Chemistry, 2025)

Fe-Mn bimetallic loaded sludge biochar as a novel periodate activator for sulfamethoxazole removal: The combination of radical and non-radical mechanisms - Yingjian Yu; Xiaolong Chen; Ling Tao; Yulong Li; Li Wu; Zhuqi Chen; Xiaoman He; Yuting Luo; Lie Yang (Environmental Research, 2025)

C4-HSL drives rapid biofilm formation in low-temperature aquaculture effluent: strengthening structural stability of biofilm and improving nitrogen removal efficiency - Junlin Li; Jiahao Ma; Zhifei Li; Jun Xie; Yuting Zhang; Mengyuan Yu; Yun Xia; Wangbao Gong; Kai Zhang; Guangjun Wang; Quanfa Zhong; Jingjing Tian; et al. (Environmental Research, 2025)

Fabrication of dual ionic polymer nanofiltration membrane with deposited graphene oxide interlayer for enhanced flux and antifouling properties - Xinyang Yu; Yihang Zhu; Yuting Lu; Mudan Wang; Zhonghua Huang (Desalination, 2025)

Redefining cyclodextrin-based systems: A multiscale framework of structure, function and application interconnection - Yu-han Zhang; Yuting Lin; Yihan Lin; Zheng Luo; Zibiao Li; Yun-Long Wu (Chemical Engineering Journal, 2025)

Computational design of indoor lighting supported by artificial intelligence: Recent advances and future prospects - Peng Chen; Lixiong Wang; Yuting Wu; Zelin Liang; Juan Yu; Tianyi Chen (Building and Environment, 2025)

Diversification of Alpine Soil Animals Corroborates Uplifts and Environmental Changes of Qinghai‐Tibetan Plateau and Himalayas: Insights From Molecular Phylogeny and Cryptic Diversity of the Isotoma quadridentata Complex (Collembola: Isotomidae) - Yating Zhang; Daoyuan Yu; Huanhuan Zhang; Chen Li; Yuting Jiang; Feng Zhang; Feng Hu; Manqiang Liu (Zoologica Scripta, 2025)
The Qinghai‐Tibetan Plateau and Himalayas (QTPH) are biodiversity hotspots crucial for understanding alpine speciation. While studies have focused on flora and aboveground fauna, the impact of QTPH uplift on soil fauna diversification remains understudied. To address this research gap, we investigated a representative taxon of alpine soil animals, the Isotoma quadridentata species complex (Collembola, Isotomidae) widespread at 2300–5100 m above sea level across the QTPH. On a molecular aspect, we sequenced 2 mitochondrial (COI, 16S) and 3 nuclear (18S, 28S D1–2, 28S D7–10) markers from 79 individuals representing different populations of this complex and related species. Based on these data, our single‐locus (ABGD, ASAP) and multi‐locus (single‐rate and multi‐rate mPTP) species delimitation analyses supported 11–15 candidate species among this complex. On a morphological aspect, colour patterns varied both between and within the candidate species, suggesting caution in their use for Isotoma diagnosis. Macrochaetotaxy was largely consistent, except in AG4, which showed a distinct pattern on the head. Macroevolutionary analyses indicated a Himalayan origin for QTPH Isotoma 5.88–10.25 million years ago (Mya), with the I. quadridentata complex originating in the adjacent Emei Mountain later. This complex diversified initially in the Emei Mountain before dispersing to the northeast QTPH and back to Himalayas 3.82–6.48 Mya, followed by further speciation. These findings link the origin and diversification of QTPH Isotoma and the I. quadridentata complex to the uplift of the QTPH and subsequent environmental changes since Miocene, supporting a potential impact of this geological event on the diversification of alpine soil fauna.

Spatiotemporal patterns and carbon balance of non-grain cultivation across China: coupling coordination analysis and multi-objective optimization - Yuting Luo; Xin Ye; Xiaowei Chuai; Xiaoxi Yu; Ying Xu; Shuai Li; Tong Wang; Ai Xiang (Environment, Development and Sustainability, 2025)

Iron-doped and nitrogen-deficient tubular carbon nitride enables synergistic photocatalysis-self-Fenton degradation of tetracycline - Fan Fan; Jiajie Yu; Junjie Jiang; Hao Xiu; Yuting Wang; Yongpeng Cui; Yajun Wang (Journal of Environmental Chemical Engineering, 2025)

Neonatal exposure to phthalates and their alternatives and associated thyroid disorders: Levels, potential health risks, and mechanisms - Yuting Chen; Xueyu Weng; Yu Hu; Jia Yin; Shuang Liu; Qingqing Zhu; Ligang Hu; Chunyang Liao; Guibin Jiang (Journal of Environmental Sciences, 2025)

Predicting oxidative stability of Camellia oil based on multimodal data fusion strategy integrating NIR and Raman spectroscopies with chemometrics - Tuo Leng; Yuting Wang; Lizhi Huang; Qiang Yu; Jianhua Xie; Yi Chen (Food Research International, 2025)

A numerical study of the morphodynamic response of reef islands under spectral waves - Yu Yao; Yuting Song; Long Chen; Changshen Li (Continental Shelf Research, 2025)

High-performance pressure and humidity dual-mode sensor based on Thiol-ene/isocyanate dual click reaction and 3D printing technology - Feiyue Zhou; Siqi Zhang; Wanqi Feng; Lixuan Yang; Yuting Xue; Yingtao Li; Jingxing Gui; Dan Yu; Wei Wang (Chemical Engineering Journal, 2025)

Tailoring hydrogen storage properties in cold rolled MgNiSi alloys: Microstructural evolution and low-temperature performance optimization - Shixin Sun; Junqi Qiu; Ziyi Guo; Haiyi Wan; Yuting Li; Hao Yang; Qing Peng; Yu'an Chen (Chemical Engineering Journal, 2025)

Understanding diurnal variability in organic matter processing by microalgal-bacterial granular sludge in lake water remediation - Changqing Chen; Yuting Shi; Bingheng Chen; Anjie Li; Quan Meng; Yu Jiang; Bin Ji (Bioresource Technology, 2025)

Deep RNA analyses for BeWo cells and placentae of HIV positive pregnant women treated with lopinavir/ritonavir - Shi Zou; Wei Guo; Miao Tan; Xuechen Yu; Jinli Liu; Qian Du; Yuting Tan; Yingjie Wu; Songjie Wu; Yanan Zhu; Yong Feng; Ke Liang (Reproductive Toxicology, 2025)

Deoxynivalenol as a cross-contaminant in foods: Simultaneous detection, combined toxicity, and sustainable mitigation technologies - Jiawen Lu; You Long; Xingtao Zhou; Yuting Wang; Qiang Yu; Chang Li; Doris Marko; Yi Chen (Food Bioscience, 2025)

Quality enhancement and metabolic mechanism of fermented sausages with Lactiplantibacillus plantarum and Companilactobacillus alimentarius - Fangrui Han; Qiancheng Wu; Shan Li; Yuting Luo; Zengkang Ding; Tong Luo; Jiesong Liang; Chenxiang Fu; Yingchen Wang; Zhongjie Yu (Food Bioscience, 2025)

Corrigendum to “Auricularia polytricha and Flammulina velutipes ameliorate inflammation and modulate the gut microbiota via regulation of NF-κB and Keap1/Nrf2 signaling pathways on DSS-induced inflammatory bowel diseases” [Food Bioscience 47 (2022) 101426] - Ivan St'eve Nguepi Tsopmejio; Miao Ding; Jiali Wei; Cong Zhao; Yu Jiang; Yuting Li; Hui Song (Food Bioscience, 2025)

Corrigendum to “Immunomodulatory effects and mechanisms research of deer antler water extract (DAWE) on cyclophosphamide-induced immunosuppressive mice based on metabolomics and microbiomics” [Food Bioscience 62 (2024) 105038] - Lingyu Liu; Jianing Sun; Mengjie Dong; Yu Jiao; Yuting Li; Wei Hu (Food Bioscience, 2025)

Loperamide-induced constipation is associated with excessive accumulation of bile acids and cholesterol in the liver of mice; attenuation by hesperidin - Jiahui Li; Dan Bi; Ya Nie; Huijuan Wu; Yuting Lei; Siping Yu; Hedong Rong; Yanhong Yang; Zili Lei (Food and Chemical Toxicology, 2025)

Three-dimensional morphodynamic modeling of reef islands in response to climate change - Yu Yao; Min Kuang; Zhongwei Zhao; Yuting Song; Long Chen (Estuarine, Coastal and Shelf Science, 2025)

Creating precise uranyl-targeted site through sulphonation within mesoporous covalent organic framework enabling high U/V selectivity and rapid uranium extraction from seawater - Zhecheng Huang; Yuxuan Liu; Xianqing Xie; Yuting Yang; Zhiwu Yu; Feng Luo (Chemical Engineering Journal, 2025)

Nanoparticles co-delivering double-stranded RNA and insecticide enhance control efficacy and overcome pest resistance - Chao Hu; Chang Yu; Jiaqing Li; Yuxi Liu; Qinghong Zeng; Hu Wan; Shun He; Yuting Li; Ping Gao; Yuntong Lv; Kunyan Zhu; Subba Reddy Palli; et al. (Chemical Engineering Journal, 2025)

NRF2 nuclear translocation and interaction with DUSP1 regulate the osteogenic differentiation of murine mandibular osteoblasts stimulated with Porphyromonas gingivalis lipopolysaccharide - Xufei Yu; Jiaqi Bao; Yingming Wei; Yuting Yang; Wenlin Yuan; Lili Chen; Zhongxiu Wang (Journal of Zhejiang University-SCIENCE B, 2025)

Nutrient-mediated changes in growth, biochemical composition, and biosilica deposition in Cyclotella cryptica - Yuting Yu; Yan Sun; Yuhang Li; Zhengfeng Zhu; Lin Zhang; Jian Li; Spiros N. Agathos; Chengxu Zhou; Jichang Han (Journal of Oceanology and Limnology, 2025)

Characterization of gypsum-bearing dolomite corrosion under the action of different karst solutions - Yuting Song; Fei Yu; Jian Li; Zhangjun Dai; Shanxiong Chen; Yong Cao (Carbonates and Evaporites, 2025)

Keystone microbial taxa identified by deep learning reveal mechanisms of phosphorus stoichiometric homeostasis in submerged macrophytes under different hydrodynamic states - Shenyang Pan; Wenlong Zhang; Feng Yan; Yanan Ding; Ferdi L. Hellweger; Jiahui Shang; Yuting Yan; Feng Yu; Yi Li (Water Research, 2025)

Imidazole-ionic liquid-assisted solvent extraction mechanism-macro perspective and molecular aspect - Jinjian Hou; Wenjuan Wang; Zanli Fu; Yuting Hu; Zhongchi Wu; Xiaojin Wu; Jianan Hu; Haiming Yu; Gaobo Yu; Jiacheng Li (Journal of Hazardous Materials, 2025)

Urban river ecosystem instability during initial restoration: Novel perspective on state transitions within key functional group of the microbial food web - Yajie Zhu; Yasong Chen; Wenlong Zhang; Yi Li; Feng Yu; Yuting Yan (Journal of Cleaner Production, 2025)

Immobilization-biotrickling filter for the removal of hydrogen sulfide: Optimal conditions and biodegradation mechanisms - Xiangle Chen; Xiaojuan Huang; Xiang Wang; Shan Zhong; Tian Liang; Wenrou Yu; Quanwei Lv; Yuting Li; Xin Huang; Chuan Huang; Li’ao Wang; Sergei Sokolov (Journal of Environmental Chemical Engineering, 2025)

Air pollution and maternal vitamin D Status: Critical time window identification and ultraviolet radiation-mediated pathways - Yuting Gong; Zeyang Li; Qiling Yao; Mengdi Zhi; Xiaoan Zhang; Junxi Zhang; Zengli Yu; Xin Zhao (International Journal of Hygiene and Environmental Health, 2025)

A twin-track therapeutic strategy for massive rotator cuff tears based on robust and piezoelectric nanocomposite hydrogel films - Jiajie Wang; Jiacheng Dai; Dejin Jiao; Jinghua Fang; Kaiwang Xu; Tengjing Xu; Xinning Yu; Kaijie Qiu; Yuting Zhong; Hongyun Song; Sunan Zhu; Siheng Wang; et al. (Chemical Engineering Journal, 2025)

Prim-O-glucosylcimifugin-loaded nanodrug hydrogel alleviates periodontitis and colitis via modulating macrophage polarization and microbiota balance - Chengye Ding; Xinjia Cai; He Zhang; Yixin Ma; Liyuan Chen; Xiaolan Wu; Min Yu; Chang Li; Hangbo Liu; Shiying Zhang; Xinmeng Shi; Ting Zhang; et al. (Chemical Engineering Journal, 2025)

Identifying the ideal habitats for authentic herbs to cope with climate warming: a case study of Forsythia suspensa - Zikang Lu; Yinfeng Yu; Yuting Liu; Xiangrui Fu; Xuhong Duan; Errong Yu; Xueqiang Guo; Jiankun Yan; Kaiyan Zheng; Xian Gu; Donglai Ma (Environmental Monitoring and Assessment, 2025)

Corrigendum to “Design, hydrodynamic analysis, and test of a manta ray-inspired soft wing for flapping wing propulsion of underwater gliders” [Ocean Eng. 327 (2025) 120998] - Yudong Guo; Yuting Li; Xiao Yu; Libing Han; Wendong Niu; Tongshuai Sun (Ocean Engineering, 2025)

Effect of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel on physicochemical, texture and sensory properties of low-fat yoghurt - Ya-Hui Yu; Luo-Bang Wu; Long-Qing Li; Ming-Yu Jin; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2025)

Gut microbiota mediated immunoregulatory effects of Dendrobium officinale polysaccharides-selenium nanoparticles complexes - Yan Long; Jiajing Yang; Hongfei Ji; Yuting Fan; Keyao Dai; Wenjie Ding; Haiyu Ji; Juan Yu (Food Bioscience, 2025)

Alternating electric field/non-thermal effect strategy driven modification of hemp seed protein: Multi-spectroscopic structural analysis, computer simulation distribution model - Ning Wang; Yuting Wang; Boyu Liu; Yiran Lian; Tong Wang; Weining Wang; Dianyu Yu (Food Hydrocolloids, 2025)

Enhanced stabilization and curcumin delivery by covalent NaCas-EGCG modified proso millet protein nanoparticles in Pickering emulsions - Yuting Fan; Jing Ren; Xinyi Li; Pingping Zhang; Yang Yao; Xiuzhu Yu; Shuang-kui Du (Food and Bioproducts Processing, 2025)

Field effect and coupling influences of urban park cold islands under varying wind speeds and heat island gradients - Chunyu Li; Yu Zhang; Hong Liang; Yang Yu; Siyu Long; Yuting Sun; Tong Wang; Kai Wang; Qian Cao (Urban Climate, 2025)

Electrocatalytic membrane-driven ozonation to reconstruct the extracellular polymeric substance for enhanced sludge dewatering - Yantao Song; Wei Zhang; Zhenao Gu; Yu Cheng; Haihua Bao; Jiaqi Wang; Ning Wang; Yuting Liu; Zongqiang Zhu; Chengzhi Hu (Journal of Water Process Engineering, 2025)

Dual-window emissive radiative cooling textiles with a PTFE/SiO2 bilayer coating for enhanced thermal management - Luxuan Zhang; Qinting Zhu; Yuting Zhou; Bo Xu; Man Zhou; Ping Wang; Qiang Wang; Yuanyuan Yu (Chemical Engineering Journal, 2025)

High-capacity Zn-ion storage in NiMnHCF/Ti3C2Tx MXene composite cathode boosted by Mn-containing electrolyte for aqueous Zn-ion hybrid capacitors - Kun Fang; Jingyuan Zhang; Jianing Yu; Yuting Hu; Jiawei Wang; Zhuo Wang; Bin Zhao (Chemical Engineering Journal, 2025)

A novel deacetylase inhibitor KLX suppresses liver fibrosis by deacetylating PPARγ through promoting ubiquitination-mediated HDAC1 degradation - Feng Zhang; Jinglun Song; Han Wu; Keying Lin; Chunlei Wang; Linghua Zeng; Xue Kong; Kunkun Zou; Hongtao Diao; Zhuo Wang; Wei Si; Weitao Jiang; et al. (Science China Life Sciences, 2025)

Gut metabolites and functional recovery after ischemic stroke: a genetic perspective - Wenpeng Wu; Luwen Zhu; Jiongliang Zhang; Xinyue Li; Donghui Yu; Yuting Wang; Yumeng Su; Xiangyu Wei; Hanwen Ma; Wenjing Song; Jinting Li; Lili Teng; et al. (Mammalian Genome, 2025)

Design, hydrodynamic analysis, and test of a manta ray-inspired soft wing for flapping wing propulsion of underwater gliders - Yudong Guo; Yuting Li; Xiao Yu; Libing Han; Wendong Niu; Tongshuai Sun (Ocean Engineering, 2025)

Selective extraction of lithium from coal gangue utilizing a two-stage roasting process - Yu Xie; Zhengwei Han; Afsar Khan; Yuting Liang; Hui Zhong; Zhiguo He (Minerals Engineering, 2025)

Multi-factor fungal growth prediction and optimal control during grain storage based on RF error compensation - Wang Li; Lu Junfeng; Jin Xuebo; Wang Xiaoyi; Yu Jiabin; Bai Yuting; Kong Jianlei; Guo Xianglan; Li Hanyu (Journal of Stored Products Research, 2025)

Rapid classification of Camellia seed varieties and non-destructive high-throughput quantitative analysis of fatty acids based on non-targeted fingerprint spectroscopy combined with chemometrics - Tuo Leng; Yuting Wang; Zhijun Wang; Xiaoyi Hu; Tongji Yuan; Qiang Yu; Jianhua Xie; Yi Chen (Food Chemistry, 2025)

Oxidative stress induced by combined glyphosate and TBBPA exposure promotes gill autophagy and inflammation via the PI3K/AKT/mTOR pathway - Mingyue Li; Shuang Lou; Kai Chen; Yuting Dong; Shize Wang; Tingting Yu; Xinrui Deng; Shu Li (Fish & Shellfish Immunology, 2025)

Surface passivated 3D halide perovskite single crystal by 2D perovskite towards high performance soft X-ray detection and gamma-ray spectrum - Yan Xiong; Min Li; Shunsheng Yuan; Yuting Liu; Tong Jin; Jincong Pang; Sihao Xia; Mingquan Liao; Lingling Liu; Lingfeng Wu; Kuan Yew Cheong; Huayang Yu; et al. (Chemical Engineering Journal, 2025)

One-stone-four-birds strategy to construct magnetic mesoporous nano-ratio fluorescence sensor for efficient discovery of PSD95-nNOS uncouplers - Tao Peng; Xu Lu; Yang Jin; Xicheng Yang; Qian Liu; Chen Chen; Wanting Zhou; Yuting Guo; Yu Zhang; Yankun Gao; Hongjuan Zhang; Hongliang He; et al. (Chemical Engineering Journal, 2025)

Research progress of non-coding RNA regulating the role of PANoptosis in diabetes mellitus and its complications - Guangyu Han; Kaibo Hu; Tianfeng Luo; Wenting Wang; Deju Zhang; Liu Ouyang; Xiao Liu; Jianping Liu; Yuting Wu; Jianqi Liang; Jitao Ling; Yixuan Chen; et al. (Apoptosis, 2025)

Food-derived peptides as novel therapeutic strategies for NLRP3 inflammasome-related diseases: a systematic review - Ziqi Zhang; Yuan Zhang; Meiying Zhang; Chenfeng Yu; Pingping Yang; Minxuan Xu; Jitao Ling; Yuting Wu; Zicheng Zhu; Yixuan Chen; Ao Shi; Xiao Liu; et al. (Critical Reviews in Food Science and Nutrition, 2025)

A novel method of species-specific molecular target mining and accurate discrimination of Bacillus cereus sensu lato - Yibing Zhao; Jihang Xie; Shubo Yu; Qingping Wu; Zhi Wang; Yuting Shang; Zhengzheng Wang; Jumei Zhang; Huichan Zhai; Zhenying Huang; Yu Ding; Juan Wang (International Journal of Food Microbiology, 2025)

Preparation and characterization of lauric acid-rich wax oleogel chocolates: Insights into crystallization behavior, storage stability, and bloom resistance - Yuting Fu; Yu Chen; Pengyan Li; Chuan Li; Zhiguo Wang; Jun Cao (Food Research International, 2025)

Effect of 4-methylbenzoquinone concentration on its covalent conjugates with β-lactoglobulin: Structural and functional properties - Jinshun Ye; Xiaotong Li; Zhenzhao Weng; Yuting Li; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Jingkun Yan; Lin Li (Food Chemistry, 2025)

Investigation of the interaction mechanism of citrus pectin-polyphenol-protein complex - Ziyan Huang; Yuting Wang; David Julian McClements; Ruihong Dong; Yu Wang; Qin Wang; Huifan Liu; Qiang Yu; Jianhua Xie; Yi Chen (Food Chemistry, 2025)

Multiple recognition-powered abiotic bimetallic oxide nanozyme-based colorimetric platform for the selective detection of allergen β-lactoglobulin - Chunda Liu; Longai Liang; Yang Yu; Yang Hou; Maosen Yuan; Yuting Zhuang; Jinyi Wang; Yue Zhang (Food Chemistry, 2025)

The impact of carbon emission trading scheme policy on information asymmetry in the stock market: Evidence from China - Xue Yuan; Yu Dong; Liang Liang; Yuting Wei (Energy Policy, 2025)

The Co‐Infection of ISKNV ‐ II and RGNNV Resulting in Mass Mortality of Juvenile Asian Seabass ( Lates calcarifer ), Zhuhai, Southern China - Qianqian Sun; Shan Ding; Xiangrong Liu; Wenfeng Zhang; Fangzhao Yu; Yuting Fu; Yong Li; Chuanfu Dong (Journal of Fish Diseases, 2025)
Infectious spleen and kidney necrosis virus (ISKNV) and nervous necrosis virus (NNV) are two common and important causative agents in marine‐cultured fish. However, high viral loads of both ISKNV and NNV in the same clinical case is unusual. In this study, a mass mortality event of Asian seabass Lates calcarifer juveniles occurred in Zhuhai, the main Asian seabass cultured area in mainland China. The fish samples were pooled for pathogen identification and both high viral loads of ISKNV and NNV were detected by real‐time microfluidic quantitative PCR and conventional PCR. Immunohistochemistry and immunofluorescence showed that strong ISKNV signals were detected in spleen and liver, while strong NNV signals were detected in brain and eye. The tissue homogenates were inoculated into MFF‐1 cell and SSN‐1 cell, respectively. After several viral passages, both individual ISKNV and NNV were purely isolated from each other, and designated as ASB‐ISKNV‐23 and ASB‐NNV‐23, respectively. The whole genome sequences of ASB‐ISKNV‐23 and ASB‐NNV‐23 were determined and annotated. The result showed that ASB‐ISKNV‐23 and ASB‐NNV‐23 are composed of 112,236 bp and 4441 bp, respectively. Phylogeny analysis showed that ASB‐ISKNV‐23 belongs to ISKNV‐II sub‐genotype and ASB‐NNV‐23 belongs to RGNNV genotype. Collectedly, coinfection of ISKNV‐II and RGNNV were firstly documented in mass mortality of Asian seabass in mainland China. Importantly, both individual ISKNV‐II and RGNNV were purely isolated using two different permissive cell lines. Our study provides useful information for better understanding the complex pathogenesis regarding the coinfection with ISKNV and NNV in farmed fish.

Correction: Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2025)

Association between maternal serum zinc and birth weight is modified by neonatal SOD2 polymorphism and promoter methylation - Yuting Zeng; Yalong Wang; Yanan He; Qinyang Li; Ruiqin Chen; Cuiping Wu; Na Li; Xinya Cheng; Yuhui Du; Fangfang Yu; Yue Ba; Guoyu Zhou (Journal of Trace Elements in Medicine and Biology, 2025)

NH2-MIL-88B(Fe)/PVDF mixed matrix membranes: A one-stone-two-birds strategy for efficient removal of tetracycline hydrochloride from aquatic systems - Simiao Zhao; Hu Zheng; Yuting Xie; Xia Zheng; Ke Liu; Yizhou Yang; Xi Chen; Yuan Xiang; Yu-Hsuan Chiao; Guangyong Zeng (Journal of Environmental Chemical Engineering, 2025)

Improvement of the gel properties of curdlan gel by hydrogen bonding interaction with trehalose - Long-Qing Li; Le-Yi Pan; Tong-Xin Liang; Mingyu Jin; Ya-Hui Yu; Xiangying Yu; Xiaozhen Liu; Fengyuan Liu; Yuting Li; Jing-Kun Yan (Food Hydrocolloids, 2025)

Roles of lncRNA in the crosstalk between osteogenesis and angiogenesis in the bone microenvironment - Shihua Zhang; Jianmin Guo; Yuting He; Zhi’ang Su; Yao Feng; Lan Zhang; Jun Zou; Xiquan Weng; Yu Yuan (Journal of Zhejiang University-SCIENCE B, 2025)

Viral metagenome analysis uncovers hidden RNA virome diversity in juvenile largemouth bass (Micropterus salmoides) - Xing Zhang; Wenbin Yu; Wenjing Shao; Zihan He; Yingzhou Lu; Yuting Xin; Zeen Shen; Yang Zhou; Xiaolong Hu (Aquaculture, 2025)

Unlocking the potential of vinegar residue: A novel biorefining strategy for amino acid-enriched xylooligosaccharides and humic-like acid - Yuanyuan Zhu; Ruijun Tang; Yuting Cao; Yongjian Yu; Junjun Zhu (Waste Management, 2025)

Distribution characteristics and ecological risk assessment of heavy metal pollution in seawater near the Yellow River Estuary of Laizhou Bay - Xiaojie Jin; Jichen Liu; Liming Wang; Xiaoxiao Yu; Jiaying Wang; Yang Jin; Shaonan Qiu; Jiaqi Liu; Yuting Zhao; Shan Sun (Marine Environmental Research, 2025)

Calculation model for CO2 emissions of blended cement production - Peng Gao; Wei Zha; Yuting Chu; Yang Yu; Binggen Zhan; Qijun Yu; Faquan Xie; Haijun Lu (Journal of Cleaner Production, 2025)

Extraction of duckweed or algal bloom covered water using the SEM-Unet based on remote sensing - Yuting Zhang; Qian Shen; Yue Yao; Yu Wang; Jiarui Shi; Qianyu Du; Ruolong Huang; Hangyu Gao; Wenting Xu; Bing Zhang (Journal of Cleaner Production, 2025)

Optimal allocation of technical reclamation and ecological restoration for a cost-effective solution in Pingshuo Opencast Coal Mine area of China - Yuting Shi; Yu Feng; Jinman Wang; Zhongke Bai; Xiaoming Feng; Bihui Chen (Journal of Environmental Management, 2025)

The geochronology and cooling history of type 7 chondrites: Insights into the early impact events on chondritic parent body - Ye Li; Yuting Wang; Haoxuan Jiang; Jia Liu; Liping Qin; Qiu-Li Li; Yu Liu; Zhenfei Wang; Weibiao Hsu (Geochimica et Cosmochimica Acta, 2025)

Full composition-wide association study identifies the chemical markers to distinguish different processed camellia oils: Integrating multi-targets with chemometrics - Ruihong Dong; Tuo Leng; Yuting Wang; Bei Gan; Qiang Yu; Jianhua Xie; Qianwen Du; Mengting Zhu; Yi Chen (Food Chemistry, 2025)

Effect of excitation voltage in a magnetically induced electric field on the physicochemical, structural and functional properties of citrus pectin - Ya-Hui Yu; Xiaozhen Liu; Luo-Bang Wu; Xiangying Yu; Ming-Yu Jin; Long-Qing Li; Fengyuan Liu; Yuting Li; Lin Li; Bing Li; Jing-Kun Yan (Food Chemistry, 2025)

Exploring the immunomodulatory mechanisms of Osmunda japonica Thunb polysaccharides: Activation of MAPK and NF-κB signaling pathways - Xiaochen Liu; Rui Xu; Yuting Miao; Yining Zang; Yuxin Huang; Yuying Zheng; Fengwei Li; Ming Wei; Rui Xiao; Xiaohong Yu (Food Bioscience, 2025)

Miniaturized and portable device for Noninvasive, ultrasensitive and point-of-care diagnosis by engineered Metal-Carbide-based field effect transistor - Wenli Zhang; Yuting Luo; Junke Tao; Geng Liu; Bei Li; Yu Teng; Jianrong Xu; Lei Feng; Zhen You (Chemical Engineering Journal, 2025)

Three-dimensional windmill-shaped CAuNP based on chirality transfer and size engineering for highly sensitive immunochromatography assay - Zhengzheng Wang; Yuting Shang; Liqing Xi; Yantao Wang; Meijing Liu; Ying Feng; Yongchun Zhong; Yusen Zhang; Qingping Wu; Juan Wang; Yu Ding (Chemical Engineering Journal, 2025)

Multiscale cellulose-based optical management films with tunable transparency and haze fabricated by different bamboo components and mechanical defibrillation approaches - Yu Chen; Yuting Zhang; Juan Long; Kaimeng Xu; Tuhua Zhong (Carbohydrate Polymers, 2025)

In vitro and in vivo analysis of rumen fermentation after supplementary niacin in high concentrated fed cattle - Yuting Wei; Xiaowen Lei; Yufei Gao; Yu Guo; Xianghui Zhao; Yanjiao Li; Xiaolong Hu; Qinghua Qiu; Kehui Ouyang (Tropical Animal Health and Production, 2025)

Greater moisture impacts on radial growth of Larix sibirica in the eastern Altay Mountains since the 1990s - Xiaoxia Gou; Tongwen Zhang; Shulong Yu; Huaming Shang; Ruibo Zhang; Li Qin; Kexiang Liu; Shengxia Jiang; Dong Guo; Yuting Fan; Ruxianguli Abudureheman; Heli Zhang (International Journal of Biometeorology, 2025)

Vertical migration and leaching behavior of antibiotic resistance genes in soil during rainfall: Impact by long-term fertilization - Yu Zhang; Yuting Zhang; Jun Xie; Chaolei Yuan; Dong Zhu; Xiaojun Shi (Water Research, 2024)

Alkaline tolerance in plants: The AT1 gene and beyond - Yuting Qi; Yujie Xie; Mingrui Ge; Wei Shen; Yu He; Xiao Zhang; Feng Qiao; Xing Xu; Quan-Sheng Qiu (Journal of Plant Physiology, 2024)

Fabrication of novel adsorptive photocatalyst GQDs/Sn3O4 for highly efficient synergistic removal of U(Ⅵ) - Yuting Deng; Jinchi Lin; Wentao Zhu; Jinhui Yang; Xiuming Yu; Zhui Tian; Shuibo Xie; Bin Yang (Journal of Environmental Chemical Engineering, 2024)

Carvacrol acts on the larval midgut of Spodoptera frugiperda by destroying the tissue structure and altering the bacterial community - Jingjing Zhang; Cuiting Liu; Xinyi Xie; Xuanyue Yu; Yuting Huang; Rui Tang; Jian Zeng; Benshui Shu (Journal of Asia-Pacific Entomology, 2024)

Polyphenol compounds contributing to the improved bioactivities of fermented Rubus chingii Hu - Yuhan Cheng; Yuting Wang; Tongji Yuan; Jianhua Xie; Qiang Yu; Yi Chen (Food Research International, 2024)

Elevating biotransamiantion of pineapple peel-derived furfural into furfurylamine by recombinant Escherichia coli carrying pyruvate decarboxylase and mutant ω-transaminase with low loading of amine donor - Yuting Liu; Yu-Cai He; Cuiluan Ma (Food Bioscience, 2024)

Immunomodulatory effects and mechanisms research of deer antler water extract (DAWE) on cyclophosphamide-induced immunosuppressive mice based on metabolomics and microbiomics - Lingyu Liu; Jianing Sun; Mengjie Dong; Yu Jiao; Yuting Li; Wei Hu (Food Bioscience, 2024)

Corrigendum to ‘A facile synthesis of Ag3PO4/BiPO4 p-n heterostructured composite as a highly efficient photocatalyst for fluoroquinolones degradation’ [Environ. Res. 203 (2022) 111843] - Xin Zhu; Yu Yan; Yuting Wang; Tao Long; Jinzhong Wan; Cheng Sun; Yang Guo (Environmental Research, 2024)

Wide-temperature zinc-iodine batteries enabling by a Zn-ion conducting covalent organic framework buffer layer - Jie Xu; Qingyu Dai; Yuting Yang; Zhangyu Zheng; Fengtao Yu; Yongjie Cao; Zhipeng Jiang; Bo Peng; Lianbo Ma (Chemical Engineering Journal, 2024)

Advanced review on type II collagen and peptide: preparation, functional activities and food industry application - Pengbo Cui; Tianlun Shao; Weilin Liu; Mengyu Li; Mingxiao Yu; Weixue Zhao; Yanzhuo Song; Yuting Ding; Jianhua Liu (Critical Reviews in Food Science and Nutrition, 2024)

Enhancing the performance of microalgal-bacterial systems with sodium bicarbonate: A step forward to carbon neutrality of municipal wastewater treatment - Yuting Shi; Bin Ji; Anjie Li; Xiaoyuan Zhang; Yu Liu (Water Research, 2024)

Efficient reclamation of phosphorus from wetland biomass waste via liquid-recirculated hydrothermal carbonization and precipitation - Junxia Wang; Yuting Wang; Fan Yu; Jiangtao Wang; Xutong Wang; Jipeng Luo; Chao He; Xiaoqiang Cui; Beibei Yan; Guanyi Chen (Water Research, 2024)

Impact of camptothecin exposures on the development and larval midgut metabolomic profiles of Spodoptera frugiperda - Xuanyue Yu; Xinyi Xie; Cuiting Liu; Yuting Huang; Huiyin Hu; Jian Zeng; Benshui Shu; Jingjing Zhang (Pesticide Biochemistry and Physiology, 2024)

NHX5/NHX6/SPY22 complex regulates BRI1 and brassinosteroid signaling in Arabidopsis - Jun Shang; Guoxiu Mu; Yuting Qi; Xiao Zhang; Wei Shen; Yujie Xie; Mingrui Ge; Yu He; Feng Qiao; Quan-Sheng Qiu (Journal of Plant Physiology, 2024)

Evaluation of potential evapotranspiration models over fluxdata network cropland sites - Ziling He; Shouzheng Jiang; Yu Feng; Lu Zhao; Jun Li; Yuting Zhang; Ningbo Cui (Journal of Hydrology, 2024)

A new approach to biotransformation and value of kitchen waste oil driven by gut microorganisms in Hermetia illucens - Yuting Wang; Zuojian Yu; Qingcheng Cao; Cuncheng Liu; Yuanhang Qin; Tielin Wang; Cunwen Wang (Journal of Environmental Management, 2024)

Biodiversity-safeguarding threshold for urea-fertilizer application on paddy fields: Protozoa-based toxicity tests - Chunyu Hou; Kexin Yu; Tianyi Shi; Benchao Jiang; Liangzi Cao; Wenyuan Wang; Mei Han; Jing Tang; Yuting Zhao; Xuming Pan; Jianye Li; Duu-Jong Lee; et al. (Journal of Environmental Management, 2024)

Investigating the temporal evolution of physicochemical attributes and flavorome profiles in Sichuan shai vinegar utilizing diverse aging techniques - Li Li; Cuixin Huang; Zhicheng Li; Yulin Zhao; Jun Liu; Yu Zheng; Rong Cao; Yuting Liao (Food Research International, 2024)

The influence of drying methods on extract content, tyrosinase activity inhibition, and mechanism in Ascophyllum nodosum: A combined microstructural and kinetic study - Yujing Lu; Yuting Wang; Yu Liu; Yuze Wang; Sainan Guo; Kailing Sun; Hang Qi (Food Chemistry, 2024)

Nrf2 affects DNA damage repair and cell apoptosis through regulating HR and the intrinsic Caspase-dependent apoptosis pathway in TK6 cells exposed to hydroquinone - Lin Chen; Pu Guo; Lu Zhai; Lingxue Yu; Delong Zhu; Xiaoyi Hu; Zhuanzhuan Li; Yuting Chen; Qian Sun; Lei Sun; Hao Luo; Huanwen Tang (Toxicology in Vitro, 2024)

Diverse metabolism drives comammox in continental-scale agricultural streams: Important ammonia oxidation but low N2O production - Shanyun Wang; Manyi Xiao; Liping Jiang; Yucheng Jin; Yuting Zhou; Longbin Yu; Gawhar Armanbek; Manting Wang; Jingchen Ma; Guibing Zhu (Science of The Total Environment, 2024)

Multiscale characterization of surfactant-enhanced coal rock pore-fracture imbibition - Qiming Huang; Yuting Yan; Bo Yu; Gang Wang; Shimin Liu; Hao Xu; Ting Liu; Mingyang Li; Xu Feng (Process Safety and Environmental Protection, 2024)

Unlocking new drying potential for Lotus root: Ultrasonic osmotic dehydration and microwave hot air drying based on phenolic retention and microstructure - Yiyang Yu; Yuting Chen; Yong Wang; Xia Sun; Yemin Guo; Dianbin Su; Huihui Xu (Innovative Food Science & Emerging Technologies, 2024)

Enhancement of bio-jet fuel production from corncob by iron ion-catalyzed hydrogen peroxide pretreatment - Rui Zhang; Yuting He; Rui Zhu; Can Zhu; Yu Jiang; Yuming Ni; Minghui Fan; Quanxin Li (Fuel, 2024)

Distinguishing α/β-linkages and linkage positions of disaccharides in galactooligosaccharides through mass fragmentation and liquid retention behaviour - Xiangying Yu; Xueying Peng; Fengyuan Liu; Yuting Li; Jingkun Yan; Lin Li (Food Chemistry, 2024)

Enhancing electricity generation from water evaporation through cellulose-based multiscale fibers network - Haoran Kong; Yuting Li; Jin Yan; Xiang Liu; Mingxue Xiang; Qinhuan Wang; Yu Wang (Chemical Engineering Journal, 2024)

Dynamic, multi-color, multi-level stimulus-responsive luminescence in a co-crystallized coordination polymer: Modulation of energy transfer by acid-induced ligand protonation and photo-induced radical generation - Yongsheng Yang; Wanting Shen; Yuting Feng; Fengqi Zhang; Zhan Yu; Tingting Lu; Zhen Zhao (Chemical Engineering Journal, 2024)

Exploiting a tumor softening targeted bomb for mechanical gene therapy of chemoresistant Triple-Negative breast cancer - Yuting Shen; Xin Guan; Shaoyue Li; Xiaodong Hou; Jifeng Yu; Haohao Yin; Xuexia Shan; Xiaoxia Han; Lifan Wang; Boyang Zhou; Xiao Li; Liping Sun; et al. (Chemical Engineering Journal, 2024)

Collaborative modelling of gas-solid reacting flow in a fuel reactor equipped with process controllers in chemical looping combustion/conversion - Guoyin Yu; Yuting Zhuo; Shuyue Li; Yansong Shen (Chemical Engineering Journal, 2024)

Distribution characteristics, sources and risk assessment of heavy metals in the surface sediments from the largest tributary of the Lancang River in the Tibet Plateau, China - Min Liu; Liangyuan Zhao; Li Lin; Yuting Zhang; Huawei Huang; Wei Deng; Yunjiao He; Jingxiang Tao; Yuan Hu; Luyi Nan; Yu Xuan Zhu (Environmental Geochemistry and Health, 2024)

The resistance to anoikis, mediated by Spp1, and the evasion of immune surveillance facilitate the invasion and metastasis of hepatocellular carcinoma - Zhengwei Zhang; Xiaoning Chen; Yapeng Li; Feng Zhang; Zhen Quan; Zhuo Wang; Yang Yang; Wei Si; Yuting Xiong; Jiaming Ju; Yu Bian; Shibo Sun (Apoptosis, 2024)
Anoikis-Related Genes (ARGs) lead to the organism manifesting resistance to anoikis and are associated with unfavorable prognostic outcomes across various malignancies.Therefore, it is crucial to identify the pivotal target genes related to anoikis in HCC .We found that ARGs were significantly correlated with prognosis and immune responses in HCC. The core gene, SPP1, notably promoted anoikis resistance and metastasis in HCC through both in vivo and in vitro studies. The PI3K-Akt-mTOR pathway played a critical role in anoikis suppression within HCC contexts. Our research unveiled SPP1’s role in enhancing PKCα phosphorylation, which in turn activated the PI3K-Akt-mTOR cascade. Additionally, SPP1 was identified as a key regulator of MDSCs and Tregs migration, directly affecting their immunosuppressive capabilities.These findings indicate that in HCC, SPP1 promoted anoikis resistance and facilitated immune evasion by modulating MDSCs and Tregs. Graphical Abstract

Study on the spatial and temporal evolutionary characteristics of ozone concentration and the impact of human activities in China in 2019 - Yongchun Wang; Wang Zhang; Yu’an Liu; Yazhu Wang; Yuting Fu; Zhaohui Feng; Lingqing Wang (Acta Geochimica, 2024)

Insomnia and stress: the mediating roles of frontoparietal network - Miao He; Yuan Li; Mengting Chen; Huiyun Li; Chunrong Liang; Yanli Chen; Chunyan Long; Yuting Yang; Jingyi Ye; Yu Mao; Yan Wang; Ling Li (Brain Imaging and Behavior, 2024)

Coping with the concurrent heatwaves and ozone extremes in China under a warming climate - Mengmeng Li; Xin Huang; Dan Yan; Shiyi Lai; Zihan Zhang; Lei Zhu; Yuting Lu; Xinyi Jiang; Nan Wang; Tijian Wang; Yu Song; Aijun Ding (Science Bulletin, 2024)

Evaluation of the expression stability of potential reference genes for RT-qPCR in Spodoptera frugipreda larvae exposed to camptothecin - Yuting Huang; Xuanyue Yu; Xinyi Xie; Cuiting Liu; Huijiao Zhang; Jiaxiang Yuan; Jintian Lin; Benshui Shu; Jingjing Zhang (Journal of Asia-Pacific Entomology, 2024)

Preconception mitochondrial DNA copy number plays a crucial role in linking prenatal air pollution with the risk of preterm birth - Qiuming Wang; Yalong Wang; Panpan Sun; Yanan He; Xi Yan; Lifang Jiang; Yuting Zeng; Jingjing Wu; Junxi Zhang; CuiPing Wu; Fangfang Yu; Yue Ba; et al. (International Journal of Hygiene and Environmental Health, 2024)

In vitro simulated digestion and fermentation characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Ya-Hui Yu; Luo-Bang Wu; Xiaozhen Liu; Li-Chao Zhao; Long-Qing Li; Ming-Yu Jin; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2024)

Exploring authenticity and potential markers of Lushan Yunwu green tea by fusing 1H NMR and UPLC-Q/TOF-MS techniques - Xiaoli Yan; Yuting Wang; Xinjin Yu; Jianhua Xie; Qiang Yu; Yi Chen (Food Control, 2024)

Influence of group VIB metals introduced into zeolite on the adsorption performance of VOCs in cooking oil fumes - Honghong Yi; Siming Guo; Yuting Yuan; Qingjun Yu; Fengshi Meng; Wenjing Wu; Shunzheng Zhao; Ya Wang; Xiaolong Tang (Chemical Engineering Journal, 2024)

Development of preferred sizes for building-integrated lighting units (BILUs) - Peng Chen; Juan Yu; Yuting Wu; Lixiong Wang; Hongbin Guo; Yuanye He (Building and Environment, 2024)

Sleep onset time as a mediator in the association between screen exposure and aging: a cross-sectional study - Senlin Lin; Meng Gao; Juzhao Zhang; Yuting Wu; Tao Yu; Yajun Peng; Yingnan Jia; Haidong Zou; Lina Lu; Deshang Li; Yingyan Ma (GeroScience, 2024)
Excessive screen exposure has become a significant health concern. This study investigates the impact of screen time on aging in middle-aged and elderly populations. Healthy working adults over 45 years old in Shanghai, China, underwent general and ocular examinations. Questionnaires collected demographics, medical history, and screen exposure details. Aging was assessed using the retinal age gap, defined as the difference between the retinal age predicted by deep learning algorithms based on fundus images and chronological age. Pathway analysis tested the mediation effect of sleep duration and onset time on the relationship between screen usage and retinal age gap. The retinal age gap increased with longer screen exposure, from 0.49 ± 3.51 years in the lowest tertile to 5.13 ± 4.96 years in the highest tertile (Jonckheere-Terpstra test, p < 0.001). Each additional hour of screen exposure accelerated the retinal age gap by 0.087 years (95% CI, 0.027, 0.148, p = 0.005) in the fully adjusted linear model. Sleep onset time mediated the impact of screen usage on the retinal age gap (indirect effect, β = 0.11; 95% CI 0.04–0.24). The impact of screen usage in a light-off environment on the retinal age gap was fully mediated by sleep onset time (indirect effect, β = 0.22; 95% CI 0.07–0.38), with the proportion being 100%. Our study identified a correlation between excessive screen time and a wider retinal age gap in middle-aged and elderly individuals, likely due to delayed sleep onset. To mitigate the adverse effects on the retina and aging, it is important to limit screen usage and avoid screens before bedtime.

The application of multi-point FBG bolt in measuring the excavation damaged zone of underground caverns - Gang Han; Shuling Huang; Xiuli Ding; Yuting Zhang; Jun He; Pengcheng Liu; Peiyang Yu; Dengxue Liu (Tunnelling and Underground Space Technology, 2024)

Reactive oxygen species-responsive nanotherapy for the prevention and treatment of cerebral ischemia–reperfusion injury - Jianglong Kong; Runxuan Chu; Junjie Wen; Hongrui Yu; Jiawen Liu; Yuting Sun; Meiru Mao; Xiaohan Ge; Zixin Jin; Weimin Huang; Na Hu; Yi Zhang; et al. (Chemical Engineering Journal, 2024)

Unveiling the comprehensive performance and safety advancements in PVC films through environmentally friendly PMgLaCe-LDH incorporation - Yongchun Li; Lijuan Qiao; Yu Tang; Zhi Jia; Xiang Guan; Zhaocai Wang; Shuo Xu; Weilu Yang; Yunfei Ma; Yuting Qiao; Bingxin Liu; Li Gao; et al. (Chemical Engineering Journal, 2024)

Volcanic lithofacies control the space in unconventional, rhyolitic hydrocarbon reservoirs: The Hailar Basin, NE China - Yuting Chen; Han Zheng; Guido Ventura; Linlin Zeng; Wei Pi; Yu Wei (Marine and Petroleum Geology, 2024)

The role of Pm-miR-184-3p in regulating the immune response in the pearl oyster Pinctada fucata martensii - Shirong Fu; Yuting Zhang; Yu Jiao; Qingheng Wang; Yuewen Deng; Xiaodong Du (Fish & Shellfish Immunology, 2024)

Force/Acid-Activated and Radical-Regulated photochromic luminescence in a binuclear Zero-Dimensional complex for multi-level anti-counterfeiting - Yongsheng Yang; Yuting Feng; Tingting Lu; Fengyang Bai; Wanting Shen; Fengqi Zhang; Zhan Yu; Zhen Zhao; Dongpeng Yan (Chemical Engineering Journal, 2024)

Development of novel fluoro-substituted rivastigmine derivatives as selective AChE inhibitors for the treatment of AD - Zhengwei Liu; Xinjuan Li; Mengqi Huang; Zhenhui Su; Qiyao Zhang; Yuting Li; Yi Zhou; Lintao Yu; Wenmin Liu; Zhipei Sang (Medicinal Chemistry Research, 2024)

Cocrystal Prediction of Nifedipine Based on the Graph Neural Network and Molecular Electrostatic Potential Surface - Yuting Wang; Yanling Jiang; Yu Zhou; Huai He; Jincao Tang; Anqing Luo; Zeng Liu; Chi Ma; Qin Xiao; Tianbing Guan; Chuanyun Dai (AAPS PharmSciTech, 2024)

Nitrogen-fixing cyanobacteria enhance microbial carbon utilization by modulating the microbial community composition in paddy soils of the Mollisols region - Xiao Liang; Yu Zhu; Huiyao Liu; Zuoming Xie; Genbao Li; Dunhai Li; Yuting Liang; Chengrong Peng (Science of The Total Environment, 2024)

Facet effect on nanosheet Co3O4 catalysts for toluene oxidation: Decisive role of Co3+ and reaction-induced oxygen vacancy - Rui Liu; Yuting Chu; Yiming Li; Kaijie Li; Tong Li; Hongbo Yu; Rui Liang; Yipei Chen; Tao Wu; Hongfeng Yin (Journal of Environmental Chemical Engineering, 2024)

Preparation, characterization, stability, and controlled release of chitosan-coated zein/shellac nanoparticles for the delivery of quercetin - Jiawen Liu; Hongrui Yu; Jianglong Kong; Xiaohan Ge; Yuting Sun; Meiru Mao; David Y. Wang; Yi Wang (Food Chemistry, 2024)

High-throughput identification of meat ingredients in adulterated foods based on centrifugal integrated purification-CRISPR array - Xinran Xiang; Jiaran Lu; Mengying Tao; Xiaowei Xu; Yaoyao Wu; Yuqing Sun; Shenghang Zhang; Huimin Niu; Yu Ding; Yuting Shang (Food Chemistry, 2024)

Effect of two different Flammulina velutipes polysaccharides on the physicochemical and digestive properties of rice starch and their interaction mechanisms - Tingting Bu; Yuting Ren; Yue Yu; Weicheng Wu; Zhiguo Zhang; Weiwei Hu; Jun Lu; Jian Wang; Ming Cai; Kai Yang; Peilong Sun (Food Bioscience, 2024)

Synergistic inhibitory effects of EGCG and chitosan or sodium alginate on 5-hydroxymethylfurfural formation in biscuits - Yilun Huang; Yuwei Liu; Wenting Liu; Huiyu Hu; Daoxue Zhou; Xiaoxiang Peng; Chang Li; Yi Chen; Qiang Yu; Yuting Wang (Food Bioscience, 2024)

Deep sequencing identified miR-193b-3p as a positive regulator of autophagy targeting Akt3 in Ctenopharyngodon idella CIK cells during GCRV infection - Hongyan Yu; Zheyan Chen; Yuting Liu; Yubang Shen; Lang Gui; Junqiang Qiu; Xiaoyan Xu; Jiale Li (Fish & Shellfish Immunology, 2024)

Constructing 3D sandwich-like structured Ti foam/TiO2−x/SnO2-Sb composite electrodes for the degradation of PPCPs - Anqi Li; Xuening Bai; Yuting Xie; Hebin Bao; Yu Yang; Miao He; Wenjing Yang; Qiwen Zhang; Yunhuai Zhang; Xueming Li (Chemical Engineering Journal, 2024)

Surface-modified silver aerogels combining interfacial regulation for electrocatalytic CO2 reduction under large current density - Wenbo Wang; Shanhe Gong; Haotian Wang; Yuting Tan; Xiaofeng Zhu; Xuexue Wang; Jun Liu; Weiting Yu; Guoxing Zhu; Xiaomeng Lv (Chemical Engineering Journal, 2024)

Correction to: Low FHL1 expression indicates a good prognosis and drug sensitivity in ovarian cancer - Xiaoying Chen; Yue Yu; Yuting Su; Lizhou Shi; Shanzhou Xie; Yi Hong; Xia Liu; Fuqiang Yin (Functional & Integrative Genomics, 2024)

Exposure to atrazine stimulates progesterone secretion and induces oxidative stress, inflammation, and apoptosis in the ovary of pseudopregnant rats - Jie Zhao; Guangjun Huang; Yuting Fu; Zhangbo Lou; Hao Yu; Wei Wang; Dagan Mao (Chemosphere, 2024)

Difference in muscle metabolism caused by metabolism disorder of rainbow trout liver exposed to ammonia stress - Yiwen Wu; Yuting Xia; Ao Hu; Guangquan Xiong; Wenjin Wu; Liu Shi; Lang Chen; Xiaojia Guo; Yu Qiao; Chunsheng Liu; Tao Yin; Lan Wang; et al. (Science of The Total Environment, 2024)

Comprehensive carbon footprint analysis of wastewater treatment: A case study of modified cyclic activated sludge technology for low carbon source urban wastewater treatment - Yuting Wang; Wenfang Gao; Longyi Lv; Xiaotian Ma; Zhijun Ren; Li Sun; Xiaoyang Liu; Pengfei Wang; Zhi Sun; Yu Tian; Guangming Zhang (Science of The Total Environment, 2024)

Recent advances in the occurrence, mechanisms, influence factors and control strategies of process contaminants in nuts: A comprehensive review - Yuwei Liu; Xiaoxiang Peng; Yilun Huang; Huiyu Hu; Chang Li; Yi Chen; Qiang Yu; Yuting Wang (Food Control, 2024)

Risk assessment of broflanilide for human and non-target terrestrial organisms in cauliflower production - Hongfang Lin; Yuanping Yang; Na Li; Siyu Liu; Lijing Yang; Yu Cheng; Huishan Sheng; Hui Li; Wanting Wen; Yongze Guo; Yuting Zhang (Environmental Research, 2024)

Seeds exhibit the most stable elemental composition with nitrogen addition in an Inner Mongolian grassland - Liuyi Yang; Huiqiu Shi; Lulu Zhang; Yuting Li; Qiuying Tian; Qiang Yu; Wen-Hao Zhang (Science of The Total Environment, 2024)

The role of fintech, natural resources and trade policy uncertainty towards SDGs in China: New insights from nonlinear approach - Dan Yu; Shenghu Wang; Yuting Yi; Yu Ren (Resources Policy, 2024)

Development and evaluation of an online monitoring single-particle optical particle counter with polarization detection - Weijie Yao; Xiaole Pan; Yu Tian; Hang Liu; Yuting Zhang; Shandong Lei; Junbo Zhang; Yinzhou Zhang; Lin Wu; Yele Sun; Zifa Wang (Journal of Environmental Sciences, 2024)

Exploring correlations between soy sauce components and the formation of thermal contaminants during low-salt solid-state fermentation - Feng Li; Yuting Wang; Hongxia Liao; You Long; Qiang Yu; Jianhua Xie; Yi Chen (Food Research International, 2024)

Disruption of intestinal epithelial permeability in the Co-culture system of Caco-2/HT29-MTX cells exposed individually or simultaneously to acrylamide and ochratoxin A - Jiawen Lu; Dan Su; Ying Yang; Mengni Shu; Yuting Wang; Xingtao Zhou; Qiang Yu; Chang Li; Jianhua Xie; Yi Chen (Food and Chemical Toxicology, 2024)

Selective reduction of chlorite to chloride in drinking water by UV/sulfite system: pathways, mechanisms, and kinetics - Qian Xiao; Yuting Duan; Hongyu Dong; Shuili Yu; Xingli Ji; Guicai Liu; Rongsheng Ning; Mingce Long (Chemical Engineering Journal, 2024)

Long non-coding RNA ENSMUST00000197208 promotes a shift in the Th17/Treg ratio via the P2X7R-NLRP3 inflammasome axis in collagen-induced arthritis - Yuting Pan; Yan Wu; Yingying Liu; Panpan Wang; Hui Huang; Jing Jin; Yuying Fang; Shuoyin Huang; Zhidan Fan; Haiguo Yu (Immunologic Research, 2024)

Widespread inversions shape the genetic and phenotypic diversity in rice - Wenchuang He; Huiying He; Qiaoling Yuan; Hai Zhang; Xiaoxia Li; Tianyi Wang; Yingxue Yang; Longbo Yang; Yuting Yang; Xiangpei Liu; Hua Wei; Hong Zhang; et al. (Science Bulletin, 2024)

Effects of resveratrol on DLD and NDUFB9 decrease in frozen semen of Mongolian sheep - Yuting Chen; Fanhua Meng; Yang Liu; Chunxiao Zhu; Yu Ling; Chunxia Liu; Lu Li; Yongbin Liu; Xiaolong He; Junwei Cao; Yanru Zhang (Cryobiology, 2024)

Development of novel chalcone derivatives as multifunctional agents for the treatment of Alzheimer’s disease - Xinjuan Li; Yuting Li; Zhengwei Liu; Qiyao Zhang; Yi Zhou; Lintao Yu; Wenmin Liu; Zhipei Sang (Medicinal Chemistry Research, 2024)

Soil and microbial C:N:P stoichiometries play vital roles in regulating P transformation in agricultural ecosystems: A review - Guanglei CHEN; Jiahui YUAN; Shenqiang WANG; Yuting LIANG; Dengjun WANG; Yiyong ZHU; Yu WANG (Pedosphere, 2024)

Activity quantification and assessment of recycled concrete powder based on the contributions of the dilution effect, physical effect and chemical effect - Cun Wang; Qijun Yu; Binggen Zhan; Peng Gao; Binglin Guo; Yuting Chu; Yuyang Chen; Pengfei Bian (Journal of Cleaner Production, 2024)

Molecular evolution of the heat shock protein family and the role of HSP30 in immune response and wound healing in lampreys (Lethenteron reissneri) - Yao Li; Yang Yu; Yuting Li; Hao Wang; Qingwei Li (Fish & Shellfish Immunology, 2024)

Mxene-based wearable self-powered and photothermal triboelectric nanogenerator patches for wound healing acceleration and tactile sensing - Meiru Mao; Jianglong Kong; Xiaohan Ge; Yuting Sun; Hongrui Yu; Jiawen Liu; Weimin Huang; David Y. Wang; Yi Wang (Chemical Engineering Journal, 2024)

Identification, characterisation and expression analysis of peanut sugar invertase genes reveal their vital roles in response to abiotic stress - Tingting Mao; Yaru Zhang; Wenwen Xue; Yu Jin; Hongfei Zhao; Yibo Wang; Shengnan Wang; Shengjie Zhuo; Feifei Gao; Yanping Su; Chunyan Yu; Xiaotong Guo; et al. (Plant Cell Reports, 2024)

Low FHL1 expression indicates a good prognosis and drug sensitivity in ovarian cancer - Xiaoying Chen; Yue Yu; Yuting Su; Lizhou Shi; Shanzhou Xie; Yi Hong; Xia Liu; Fuqiang Yin (Functional & Integrative Genomics, 2024)

Crop diversification promotes soil aggregation and carbon accumulation in global agroecosystems: A meta-analysis - Guorui Li; Chaoyang Yu; Pengfei Shen; Yuting Hou; Zhangheng Ren; Na Li; Yuncheng Liao; Tong Li; Xiaoxia Wen (Journal of Environmental Management, 2024)

Imbibition behavior of water on coal surface and the impact of surfactant - Qiming Huang; Yuting Yan; Gang Wang; Jingna Xie; Yifeng Huang; Mingyang Li; Bo Yu; Xu Feng (Fuel, 2024)

Vertical distribution of VOCs in the boundary layer of the Lhasa valley and its impact on ozone pollution - Dan Yao; Yinghong Wang; Zhixuan Bai; Mengtian Cheng; Guiqian Tang; Yuting Liu; Deqing Zhuoga; Hao Yu; Jianchun Bian; Yuesi Wang (Environmental Pollution, 2024)

Two-Omics Probe on the Potential of Pseudomonas sp. GDMCC 1.1703 Under Phenol Stress - Hongfei Zhu; Jiashuai Yu; Yuting Fu; Xiaoshuang Mao; Haimei Yang (Current Microbiology, 2024)

Mitigating ammonia volatilization in rice cultivation: The impact of partial organic fertilizer substitution - Bin Liao; Ping Liao; Ronggui Hu; Tianchi Cai; Yuting Zhang; Qian Yu; Bochao Zhang; Yonghong Shu; Jiaer Wang; Yufeng Luo; Yuanlai Cui (Chemosphere, 2023)

Alternative states in microbial communities during artificial aeration: Proof of incubation experiment and development of recurrent neural network models - Haolan Wang; Wenlong Zhang; Xing Hou; Jiaxin Tong; Feng Yu; Yuting Yan; Longfei Wang; Bo Zhao; Wenming Yan; Yi Li (Water Research, 2023)

Development of alantolactone-loaded zein and shellac nanoparticles for controlled release in simulated gastrointestinal digestion - Hongrui Yu; Xiaohan Ge; Jianglong Kong; Yuting Sun; Meiru Mao; Jiawen Liu; Jiaxing Ye; Amit Arora; Inthawoot Suppavorasatit; Yi Wang (Journal of Food Engineering, 2023)

Recovery of valuable elements from solid waste with the aid of external electric field: A review - Yusufujiang Mubula; Mingming Yu; Delong Yang; Bo Lin; Yuting Guo; Tingsheng Qiu (Journal of Environmental Chemical Engineering, 2023)

MiR-7-5p targeted Rb regulating cell cycle is involved in hydroquinone-induced malignant progression in human lymphoblastoid TK6 cells - Lu Zhai; Yuting Gao; Zheming Cui; Lin Chen; Lingxue Yu; Pu Guo; Delong Zhu; Huanwen Tang; Xin Liu; Hao Luo (Food and Chemical Toxicology, 2023)

Short-term prediction of the significant wave height and average wave period based on the variational mode decomposition–temporal convolutional network–long short-term memory (VMD–TCN–LSTM) algorithm - Qiyan Ji; Lei Han; Lifang Jiang; Yuting Zhang; Minghong Xie; Yu Liu (Ocean Science, 2023)
The present work proposes a prediction model of significant wave height (SWH) and average wave period (APD) based on variational mode decomposition (VMD), temporal convolutional networks (TCNs), and long short-term memory (LSTM) networks. The wave sequence features were obtained using VMD technology based on the wave data from the National Data Buoy Center. Then the SWH and APD prediction models were established using TCNs, LSTM, and Bayesian hyperparameter optimization. The VMD–TCN–LSTM model was compared with the VMD–LSTM (without TCN cells) and LSTM (without VMD and TCN cells) models. The VMD–TCN–LSTM model has significant superiority and shows robustness and generality in different buoy prediction experiments. In the 3 h wave forecasts, VMD primarily improved the model performance, while the TCN had less of an influence. In the 12, 24, and 48 h wave forecasts, both VMD and TCNs improved the model performance. The contribution of the TCN to the improvement of the prediction result determination coefficient gradually increased as the forecasting length increased. In the 48 h SWH forecasts, the VMD and TCN improved the determination coefficient by 132.5 % and 36.8 %, respectively. In the 48 h APD forecasts, the VMD and TCN improved the determination coefficient by 119.7 % and 40.9 %, respectively.

Release characteristic of bound polyphenols from tea residues insoluble dietary fiber by mixed solid-state fermentation with cellulose degrading strains CZ-6 and CZ-7 - Jingyu Si; Jiayan Xie; Bing Zheng; Jianhua Xie; Yi Chen; Chaoran Yang; Nan Sun; Yuting Wang; Xiaobo Hu; Qiang Yu (Food Research International, 2023)

Chemobiocatalytic transfromation of biomass into furfurylamine with mixed amine donor in an eco-friendly medium - Yuting Liu; Lei Li; Cuiluan Ma; Yu-Cai He (Bioresource Technology, 2023)

MBRARN: multibranch residual attention reconstruction network for medical image fusion - Weihao Zhang; Yuting Lu; Haodong Zheng; Lei Yu (Medical & Biological Engineering & Computing, 2023)

Femtomolar endogenous adenosine triphosphate-responded photoelectrochemical biosensor based on Au@Cu2O core-shell nanocubes for the ultrasensitive determination of Escherichia coli O157:H7 in foods - Shuhao Hu; Yuting Liu; Liu Liu; Zhenzhong Yu; Ning Gan (Analytica Chimica Acta, 2023)

Drivers of microbially and plant‐derived carbon in topsoil and subsoil - Weigen Huang; Yakov Kuzyakov; Shuli Niu; Yu Luo; Bo Sun; Jiabao Zhang; Yuting Liang (Global Change Biology, 2023)
Plant‐ and microbially derived carbon (C) are the two major sources of soil organic matter (SOM), and their ratio impacts SOM composition, accumulation, stability, and turnover. The contributions of and the key factors defining the plant and microbial C in SOM along the soil profile are not well known. By leveraging nuclear magnetic resonance spectroscopy and biomarker analysis, we analyzed the plant and microbial C in three soil types using regional‐scale sampling and combined these results with a meta‐analysis. Topsoil (0–40 cm) was rich in carbohydrates and lignin (38%–50%), whereas subsoil (40–100 cm) contained more proteins and lipids (26%–60%). The proportion of plant C increases, while microbial C decreases with SOM content. The decrease rate of the ratio of the microbially derived C to plant‐derived C (C M:P ) with SOM content was 23%–30% faster in the topsoil than in the subsoil in the regional study and meta‐analysis. The topsoil had high potential to stabilize plant‐derived C through intensive microbial transformations and microbial necromass formation. Plant C input and mean annual soil temperature were the main factors defining C M:P in topsoil, whereas the fungi‐to‐bacteria ratio and clay content were the main factors influencing subsoil C M:P . Combining a regional study and meta‐analysis, we highlighted the contribution of plant litter to microbial necromass to organic matter up to 1‐m soil depth and elucidated the main factors regulating their long‐term preservation.

QSAR in natural non-peptidic food-related compounds: Current status and future perspective - Yi Zhao; Yuting Xia; Yuandong Yu; Guizhao Liang (Trends in Food Science & Technology, 2023)

Refractory black carbon aerosols in rainwater in the summer of 2019 in Beijing: Mass concentration, size distribution and wet scavenging ratio - Shandong Lei; Baozhu Ge; Hang Liu; Jiannong Quan; Danhui Xu; Yuting Zhang; Weijie Yao; Lu Lei; Yu Tian; Qi Liao; Xiaoyong Liu; Jie Li; et al. (Journal of Environmental Sciences, 2023)

A dual receptor targeting and blood–brain barrier penetrating co-drug-loaded particle mediating inhibition of oxidative phosphorylation for targeted therapy of glioblastoma - Yuting Sun; Jianglong Kong; Xiaohan Ge; Meiru Mao; Hongrui Yu; Jiawen Liu; Yi Wang (Chemical Engineering Journal, 2023)

Targeting mitochondrial dynamics by AZD5363 in triple-negative breast cancer MDA-MB-231 cell–derived spheres - Yingqiang Fu; Wei Dong; Yuting Xu; Lin Li; Xin Yu; Yuheng Pang; Liujia Chan; Yuhan Deng; Cheng Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Breast cancer stem cells (BCSCs) have been suggested to contribute to chemotherapeutic resistance and disease relapse in breast cancer. Thus, BCSCs represent a promising target in developing novel breast cancer treatment strategies. Mitochondrial dynamics in BCSCs were recently highlighted as an available approach for targeting BCSCs. In this study, a three-dimensional (3D) cultured breast cancer stem cell spheres model was constructed. Mitochondrial dynamics and functions were analyzed by flow cytometry and confocal microscopy. We have demonstrated that the protein levels of FIS 1 and Mitofusin 1 were significantly increased in BCSCs. Moreover, Capivasertib (AZD5363) administration could suppress Mitofusin1 expression in BCSCs. Our use of MitoTracker Orange and annexin V double-staining assay suggested that AZD5363 could induce apoptosis in BCSCs. The sensitivity of stem cell spheres to doxorubicin was investigated by CCK8 assay, and our results indicated that AZD5363 could re-sensitize BCSCs to Doxo. Flow cytometry analysis identified doxo-induced CD44 and CD133 expression in BCSCs could be suppressed by AZD5363. In combination with AZD536, doxo-induced apoptosis in the BCSCs was significantly increased. In conclusion, our study explored, for the first time, that AZD5363 could target mitochondrial dynamics in 3D cultured stem cell spheres (BCSCs) by regulating Mitofusin.

Soil organic carbon fractions in response to soil, environmental and agronomic factors under cover cropping systems: A global meta-analysis - Qijuan Hu; Ben W. Thomas; David Powlson; Yingxiao Hu; Yu Zhang; Xie Jun; Xiaojun Shi; Yuting Zhang (Agriculture, Ecosystems & Environment, 2023)

Exploring the construction of urban artificial light ecology: a systematic review and the future prospects of light pollution - Qingli Hao; Lixiong Wang; Gang Liu; Zhuofei Ren; Yuting Wu; Zejun Yu; Juan Yu (Environmental Science and Pollution Research, 2023)

The enantioselective environmental fate of mandipropamid in water-sediment microcosms: Distribution, degradation, degradation pathways and toxicity assessment - Jing Zhang; Yanhong Li; Yuting Tan; Yu Zhang; Rui Li; Liangliang Zhou; Minghua Wang (Science of The Total Environment, 2023)

Electromagnetic field-assisted low-temperature ammonia synthesis - Bao Shun Zhang; Yuting Wang; Na Zhang; Jiewei Zhu; Wangyang Ji; Fanpeng Chen; Xing Chen; Yifu Yu; Bin Zhang (Science Bulletin, 2023)

Simultaneous and rapid screening of live and dead E. coli O157:H7 with three signal outputs: An all-in-one biosensor using phage-apoferritin@CuO2 signal tags on MXenes-modified electrode platform - Shu Xiao; Cong Cao; Tinghong Ming; Yuting Cao; Zhenzhong Yu; Ning Gan (Journal of Hazardous Materials, 2023)

Fermentation of grapefruit peel by an efficient cellulose-degrading strain, (Penicillium YZ-1): Modification, structure and functional properties of soluble dietary fiber - Wenjie Ma; Yuting Liang; Huasi Lin; Yi Chen; Jianhua Xie; Fengling Ai; Ziwen Yan; Xiaobo Hu; Qiang Yu (Food Chemistry, 2023)

Immunomodulatory effects of one novel microRNA miR-63 in pearl oyster Pinctada fucata martensii - Meiqi Dai; Yuting Zhang; Yu Jiao; Yuewen Deng; Xiaodong Du; Chuangye Yang (Fish & Shellfish Immunology, 2023)

The contribution of genotype-guided selection of P2Y12 inhibitor on prognosis in ACS /CCS patients undergoing percutaneous coronary intervention: a retrospective cohort study - Yan Wu; Dongbiao Yu; Lei Zhang; Yuting Wu; Bing Shu; Likun Ma; Tianlu Shi (European Journal of Clinical Pharmacology, 2023)

Root and hyphal interactions influence N transfer by arbuscular mycorrhizal fungi in soybean/maize intercropping systems - Tantan Zhang; Lingling Yu; Yuting Shao; Jianwu Wang (Fungal Ecology, 2023)

Poly(ionic liquid) additive: Aqueous electrolyte engineering for ion rectifying and calendar corrosion relieving - Jinbin Luo; Xinwei Jiang; Yuting Huang; Wenqi Nie; Xingcan Huang; Benjamin Tawiah; Xinge Yu; Hao Jia (Chemical Engineering Journal, 2023)

A novel AD theranostic platform with NIR-II laser controlled drug release and real-time monitoring of therapeutic outcomes - Zhili Qiu; Guojun Cao; Shanrong Lv; Dehong Yu; Jingjing Fu; Hanrong Yan; Yuting Li; Peng Zhou; Xiunan Wu; Zhao Liu; Fenglei Gao (Chemical Engineering Journal, 2023)

Suitability comparison of heuristic algorithms for the execution of lighting design objectives (LiDOs) procedure - Peng Chen; Lixiong Wang; Aiying Wang; Juan Yu; Guangyan Kong; Yuting Wu (Building and Environment, 2023)

Microphysical characteristics of black carbon from various emission sources - Hang Liu; Xiaole Pan; Shandong Lei; Yuting Zhang; Aodong Du; Yu Tian; Weijie Yao; Jinyuan Xin; Jie Li; Yele Sun; Junji Cao; Zifa Wang (Atmospheric Environment, 2023)

East Asia dust storms in spring 2021: Transport mechanisms and impacts on China - Tian Yu; Pan Xiaole; Jing Yujie; Zhang Yuting; Yao Weijie; Liu Hang; Lei Shandong; Wang Zifa (Atmospheric Research, 2023)

Oxidase-like Fe–N/C single atom nanozyme enables sensitive detection of ascorbic acid and acid phosphatase - DanDan Yang; Jingqi Chen; Yuting Huang; Ganghui Chen; Xueliang Liu; Xuan Wang; Like Yang; Zhaohui Li; Jie Hu; Qi Zhou; Jia Ge; Yu Yang (Analytica Chimica Acta, 2023)

Production of potassium-enriched biochar from Canna indica: Transformation and release of potassium - Guanyi Chen; Yuting Wang; Jiangtao Wang; Junxia Wang; Fan Yu; Qingxu Ma; Zhanjun Cheng; Beibei Yan; Yuchao Song; Xiaoqiang Cui (Waste Management, 2023)

Enhancing charge separation/transfer based on Co(II) doped tubular g-C3N4 for photoelectrochemical atrazine aptasensing - Yu Zhang; Guanyu Wu; Yun Chen; Pengcheng Yan; Li Xu; Junchao Qian; Feng Chen; Yuting Yan; Henan Li (Journal of Environmental Chemical Engineering, 2023)

Deterioration of muscle quality caused by ammonia exposure in rainbow trout (Oncorhynchus mykiss) - Yiwen Wu; Manman Zhao; Yuting Xia; Weiqing Sun; Guangquan Xiong; Liu Shi; Yu Qiao; Wenjing Wu; Anzi Ding; Lang Chen; Lan Wang; Sheng Chen (Food Bioscience, 2023)

Identification and comparative analysis of miRNA transcriptomes after allograft and xenograft transplantation in Pinctada fucata martensii - Xueru Liang; Yuting Zhang; Yu Jiao; Jieni Mai; Yuewen Deng; Xiaodong Du (Fish & Shellfish Immunology, 2023)

A mandarinfish Siniperca chuatsi infection and vaccination model for SDDV and efficacy evaluation of the formalin-killed cell vaccine in yellowfin seabream Acanthopagrus latus - Yuting Fu; Yong Li; Jiaming Chen; Fangzhao Yu; Xiangrong Liu; Weixuan Fu; Hongrun Pan; Wangdong Li; Shaoping Weng; Jianguo He; Chuanfu Dong (Aquaculture, 2023)

ATG16L1 negatively regulates MAVS-mediated antiviral signaling in black carp Mylopharyngodon piceus - Yunfan He; Yuqing Peng; Xiaoyu Liu; Jiamin Yu; Yuting Du; Zhiming Li; Hui Wu; Jun Xiao; Hao Feng (Fish & Shellfish Immunology, 2023)

Interpenetrating network expansion sponge based on chitosan and plasma for ultrafast hemostasis of arterial bleeding wounds - Yuting Shi; Wenwen Yu; Xiaoqin Liang; Ju Cheng; Yufei Cao; Mingsheng Liu; Yu Fang; Zheng Yang; Hongbin Liu; Hua Wei; Guanghui Zhao (Carbohydrate Polymers, 2023)

Size–resolved mixing state of ambient refractory black carbon aerosols in Beijing during the XXIV Olympic winter games - Yuting Zhang; Hang Liu; Shandong Lei; Aodong Du; Weijie Yao; Yu Tian; Yele Sun; Jinyuan Xin; Jie Li; Junji Cao; Zifa Wang; Xiaole Pan (Atmospheric Environment, 2023)

A comprehensive pan-cancer analysis reveals cancer-associated robust isomiR expression landscapes in miRNA arm switching - Li Guo; Dekang Ren; Yuting Zhang; Qiushi Wang; Shiyi Yu; Xinru Xu; Lulu Luo; Jiafeng Yu; Tingming Liang (Molecular Genetics and Genomics, 2023)

Microfluidic intestine-on-a-chip: Current progress and further perspectives of probiotic-foodborne pathogen interactions - Xinran Xiang; Xinbin Wang; Yuting Shang; Yu Ding (Trends in Food Science & Technology, 2023)

Status and prospects of tree-ring research in Central Asia - Tongwen Zhang; Kexiang Liu; Yuting Fan; Shulong Yu; Ruibo Zhang; Huaming Shang; Yujiang Yuan; Wenshou Wei; Qing He; Heli Zhang; Bakytbek Ermenbaev; Rysbek Satylkanov; et al. (Dendrochronologia, 2023)

Climate response of Picea schrenkiana based on tree-ring width and maximum density - Xiaoxia Gou; Tongwen Zhang; Shulong Yu; Kexiang Liu; Ruibo Zhang; Huaming Shang; Li Qin; Yuting Fan; Shengxia Jiang; Heli Zhang; Dong Guo (Dendrochronologia, 2023)

Differential therapeutic activity of a cargo-free nanoparticle in eosinophilic and neutrophilic asthma mouse models - Xiali Liu; Huasheng Zhang; Huiqiang Ma; Jiameng Gong; Kaifeng Huang; Lu Wang; Yuting Ji; Liya Sun; Xiaoyu Wang; Li Li; Lei Shen; Shan-Yu Fung; et al. (Chemical Engineering Journal, 2023)

Dual role of NR4A1 in porcine ovarian granulosa cell differentiation and granulosa-lutein cell regression in vitro - Hao Yu; Jie Zhao; Xiaomeng Pei; Yuting Xia; Haolin Li; Wei Wang; Dagan Mao (Theriogenology, 2023)

Effects of selected Bacillus strains on the biogenic amines, bioactive ingredients and antioxidant capacity of shuidouchi - Yuting Chen; Wenshan Luo; Manqin Fu; Yuanshan Yu; Jijun Wu; Yujuan Xu; Lu Li (International Journal of Food Microbiology, 2023)

Triphase dynamic extraction system involved with ionic liquid and deep eutectic solvent for various bioactive constituents from Tartary buckwheat simultaneously - Xueting Feng; Yu Cao; Yuting Qin; Siyu Zhao; Sara Toufouki; Shun Yao (Food Chemistry, 2023)

Multi-functional pH-sensitive active and intelligent packaging based on highly cross-linked zein for the monitoring of pork freshness - Jianglong Kong; Xiaohan Ge; Yuting Sun; Meiru Mao; Hongrui Yu; Runxuan Chu; Yi Wang (Food Chemistry, 2023)

Global ambient particulate matter pollution and neurodegenerative disorders: a systematic review of literature and meta-analysis - Yuting Gong; Xiaoan Zhang; Xin Zhao; Hui Chang; Junxi Zhang; Zhan Gao; Yang Mi; Yao Chen; Huanhuan Zhang; Cunrui Huang; Zengli Yu (Environmental Science and Pollution Research, 2023)

Development of a low-density SNP genotyping panel by a novel technology mGPS and its application in germplasm identification of abalone - Weihong Lin; Qizhen Xiao; Feng Yu; Zhaofang Han; Junyu Liu; Wenzhu Peng; Zekun Huang; Yuting Lei; Weiguo Li; Weiwei You; Xuan Luo; Caihuan Ke (Aquaculture, 2023)

Impact of salt deposition induced by water evaporation on petrophysical properties and pore structure in underground gas storage through dynamic and static experiments - Yong Tang; Ning Wang; Youwei He; Yong Wang; Yuting Shan; Haochuan Zhang; Yu Sun (Journal of Hydrology, 2023)

The disintegration mechanism analysis of soft rock due to water intrusion based on discrete element method - Haitao Yu; Zhibin Liu; Yun Zhang; Tingyi Luo; Yasen Tang; Qingsong Zhang; Yuting Wang (Computers & Geosciences, 2023)

Unveiling the quantification minefield in electrocatalytic urea synthesis - Yanmei Huang; Yuting Wang; Yang Liu; Aijing Ma; Jianzhou Gui; Chaoxin Zhang; Yifu Yu; Bin Zhang (Chemical Engineering Journal, 2023)

Discovering dominant ammonia assimilation: Implication for high-strength nitrogen removal in full scale biological treatment of landfill leachate - Lei Xu; Yuting Chen; Zheng Wang; Yu Zhang; Yueling He; Ai Zhang; Hong Chen; Gang Xue (Chemosphere, 2023)

Corrigendum to: Impacts of farmland application of antibiotic-contaminated manures on the occurrence of antibiotic residues and antibiotic resistance genes in soil: A meta-analysis study [Chemosphere 300 (Aug 2022) 134529] - Yu Zhang; Dengmiao Cheng; Jun Xie; Yuting Zhang; Yu Wan; Yueqiang Zhang; Xiaojun Shi (Chemosphere, 2023)

Auto-floating oxygenic microalgal-bacterial granular sludge - Yuting Shi; Bin Ji; Xiaoyuan Zhang; Yu Liu (Science of The Total Environment, 2023)

Associations between DNA methylation and genotoxicity among lead-exposed workers in China - Tuanwei Wang; Yu Meng; Yuting Tu; Guanghui Zhang; Kan Wang; Shiyang Gong; Yunxia Zhang; Tongshuai Wang; Anqi Li; David C. Christiani; William Au; Zhao-lin Xia (Environmental Pollution, 2023)

Role of melatonin receptor 1B gene polymorphism and its effect on the regulation of glucose transport in gestational diabetes mellitus - Lijie Wei; Yi Jiang; Peng Gao; Jingyi Zhang; Xuan Zhou; Shenglan Zhu; Yuting Chen; Huiting Zhang; Yuanyuan Du; Chenyun Fang; Jiaqi Li; Xuan Gao; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Characteristics of Zn Content and Localization, Cu–Zn SOD, and MT Levels in the Tissues of Marginally Zn-Deficient Mice - Ziqiong Wang; Cheng Peng; Yuting Zhang; Lei Wang; Lu Yu; Chunhong Wang (Biological Trace Element Research, 2023)

A novel aggregation-induced emission probe-linked phage sorbent assay for virulent bacteria strain imaging and on-site detection - Jiahui Teng; Cong Cao; Zhenzhong Yu; Hongzhen Xie; Fubang Liu; Chong Xu; Yuting Cao; Ning Gan (Analytica Chimica Acta, 2023)

Evolution of Meteorological Conditions during a Heavy Air Pollution Event under the Influence of Shallow Foehn in Urumqi, China - Xia Li; Keming Zhao; Shiyuan Zhong; Xiaojing Yu; Zhimin Feng; Yuting Zhong; Ayitken Maulen; Shuting Li (Advances in Atmospheric Sciences, 2023)

Differential bone metabolism and protein expression in mice fed a high-fat diet versus Daurian ground squirrels following natural pre-hibernation fattening - Xuli Gao; Shenyang Shen; Qiaohua Niu; Weilan Miao; Yuting Han; Ziwei Hao; Ning An; Yingyu Yang; Yu Zhang; Han Zhang; Kenneth B. Storey; Hui Chang (Journal of Zhejiang University-SCIENCE B, 2022)

Transport Patterns and Potential Sources of Atmospheric Pollution during the XXIV Olympic Winter Games Period - Yuting Zhang; Xiaole Pan; Yu Tian; Hang Liu; Xueshun Chen; Baozhu Ge; Zhe Wang; Xiao Tang; Shandong Lei; Weijie Yao; Yuanzhe Ren; Yongli Tian; et al. (Advances in Atmospheric Sciences, 2022)
The attainment of suitable ambient air quality standards is a matter of great concern for successfully hosting the XXIV Olympic Winter Games (OWG). Transport patterns and potential sources of pollutants in Zhangjiakou (ZJK) were investigated using pollutant monitoring datasets and a dispersion model. The PM 2.5 concentration during February in ZJK has increased slightly (28%) from 2018 to 2021, mostly owing to the shift of main potential source regions of west-central Inner Mongolia and Mongolian areas (2015–18) to the North China Plain and northern Shanxi Province (NCPS) after 2018. Using CO as an indicator, the relative contributions of the different regions to the receptor site (ZJK) were evaluated based on the source-receptor-relationship method (SRR) and an emission inventory. We found that the relative contribution of pollutants from NCPS increased from 33% to 68% during 2019–21. Central Inner Mongolia (CIM) also has an important impact on ZJK under unfavorable weather conditions. This study demonstrated that the effect of pollution control measures in the NCPS and CIM should be strengthened to ensure that the air quality meets the standard during the XXIV OWG.

The role of meteorological factors in suicide mortality in Wuhu, a humid city along the Yangtze River in Eastern China - Lingxiang Yu; Tingting Zhou; Ming Shao; Tao Zhang; Jinian Wang; Yubo Ma; Shanshan Xu; Yuting Chen; Jiansheng Zhu; Faming Pan (Environmental Science and Pollution Research, 2022)

Ser68 phosphoregulation is essential for CENP-A deposition, centromere function and viability in mice - Yuting Liu; Kehui Wang; Li Huang; Jicheng Zhao; Xinpeng Chen; Qiang Wu; Zhouliang Yu; Guohong Li (Science China Life Sciences, 2022)

Monte Carlo seismic response analysis of permafrost sites: a case study - Xiaobo Yu; Rui Zhang; Yushun Cheng; Yuting Hu (Natural Hazards, 2022)

Proteomic analysis of coarse and fine skin tissues of Liaoning cashmere goat - Zhixian Bai; Yanan Xu; Ming Gu; Weidong Cai; Yu Zhang; Yuting Qin; Rui Chen; Yinggang Sun; Yanzhi Wu; Zeying Wang (Functional & Integrative Genomics, 2022)

A neuropsin-based optogenetic tool for precise control of Gq signaling - Ruicheng Dai; Tao Yu; Danwei Weng; Heng Li; Yuting Cui; Zhaofa Wu; Qingchun Guo; Haiyue Zou; Wenting Wu; Xinwei Gao; Zhongyang Qi; Yuqi Ren; et al. (Science China Life Sciences, 2022)

Cellulomonas triticagri sp. nov., isolated from the rhizosphere soil of wheat (Triticum aestivum L.) - Chuanyu Han; Yuting Zhang; Bing Yu; Qiqi Shan; Junwei Zhao; Haoran Shi; Yuanyuan Tian; Yan Zhang; Chunyu Zhu; Wensheng Xiang (Archives of Microbiology, 2022)

An inactivating mutation in the vacuolar arginine exporter gene Vae results in culture degeneration in the fungus Metarhizium robertsii - Hui Song; Yuting Bao; Mingxiang Zhang; Shuxing Liu; Chaonan Yu; Jin Dai; Congcong Wu; Dan Tang; Weiguo Fang (Environmental Microbiology, 2022)
Summary Culture degeneration usually results in great commercial losses in the economically important filamentous fungi, but the genetic causes of the degeneration remain elusive. In the fungus Metarhizium robertsii , we found that deletion of the vacuolar arginine exporter gene Vae caused culture degeneration. Compared to the WT strain, the mutant showed increased apoptosis, reactive oxygen species (ROS) level and mitochondrial membrane potential collapse, reduced conidial yield and abnormal lipid droplet formation. The extent of the degeneration in the mutant gradually increased over the successive subculturing, which eventually became irreversible; compared to the third subculture of the mutant, the seventh subculture showed a lower conidial yield and pathogenicity to insects, stronger apoptosis, higher ROS level and a smaller number of conidial lipid droplets. Incorporation of the genomic clone of Vae could not restore the WT phenotypes in the seventh subculture, but could in the third one. Loss‐of‐function in Vae resulted in vacuolar arginine accumulation and reduction in the cytosolic arginine. This downregulated the expression of the regulator CAG9 of G protein signalling pathway, which accounted for most of the phenotypic changes associated with the degeneration of the mutant. We identified a deleterious mutation that causes culture degeneration in a filamentous fugus.

Dynamic characteristics of snow frequency and its relationship with climate change on the Tibetan plateau from 2001 to 2015 - Jinbao Liu; Yuting Li; Jing Yu; Yunjun Yao (Earth Science Informatics, 2022)

Cultivation of gut microorganisms of the marine ascidian Halocynthia roretzi reveals their potential roles in the environmental adaptation of their host - Yang Yang; Yuting Zhu; Haiming Liu; Jiankai Wei; Haiyan Yu; Bo Dong (Marine Life Science & Technology, 2022)
It has long been known that abundant symbiotic bacteria exist in the tunic and gut of marine ascidians, and that these play crucial roles in host development, physiological metabolism, and environmental adaptation. However, the identity, roles and functions of these symbiotic bacteria are known for only a few strains. In this study, we isolated and cultivated 263 strains of microorganisms from the intestine of the marine ascidian Halocynthia roretzi through a combination of aerobic and anaerobic culture approaches. Most cultivated species, both aerobic and anaerobic, from ascidian stool samples belonged to the genus Bacillus based on 16S rDNA sequencing identification and phylogenetic assays. The distribution of cultured bacteria varied with seasonal changes in environmental conditions. To explore the functions of cultured bacteria, we screened out a strain of Serratia sp. whose extracts showed high antibacterial activity against aquatic pathogens. These findings revealed the potential roles of gut microorganisms in ascidian defense and environmental adaptation, thus providing insights into the interaction and co-evolution between gut bacteria and their hosts.

Enhanced genome editing to ameliorate a genetic metabolic liver disease through co-delivery of adeno-associated virus receptor - Shuming Yin; Lie Ma; Tingting Shao; Mei Zhang; Yuting Guan; Liren Wang; Yaqiang Hu; Xi Chen; Honghui Han; Nan Shen; Wenjuan Qiu; Hongquan Geng; et al. (Science China Life Sciences, 2022)

Processing body (P-body) and its mediators in cancer - Bernard Nsengimana; Faiz Ali Khan; Ebenezeri Erasto Ngowi; Xuefeng Zhou; Yu Jin; Yuting Jia; Wenqiang Wei; Shaoping Ji (Molecular and Cellular Biochemistry, 2022)

Two new benzoic acid derivatives from endophytic fungus Aspergillus versicolor - Yanqing Ye; Yanjun Chen; Yuting Hou; Hongmei Yu; Lijun Zhu; Yanqi Sun; Min Zhou; Yijian Chen; Miao Dong (Natural Product Research, 2022)

Interactions between commensal bacteria and viral infection: insights for viral disease control in farmed animals - Chao Ran; Yu Li; Xufa Ma; Yadong Xie; Mingxu Xie; Yuting Zhang; Wei Zhou; Yalin Yang; Zhen Zhang; Li Zhou; Kaijian Wei; Zhigang Zhou (Science China Life Sciences, 2021)

Omega-3 fatty acid protects cardiomyocytes against hypoxia-induced injury through targeting MiR-210-3p/CASP8AP2 axis - Xueju Yu; Fengyao Liu; Yuting Liu; Bingqing Bai; Han Yin; Haochen Wang; Yingqing Feng; Huan Ma; Qingshan Geng (Molecular and Cellular Biochemistry, 2021)

Impact analysis of different axis layouts of detached breakwater on flow and sediment transport - Haitao Yu; Feng Luo; Ruijie Li; Yanran Liu; Xuwen Fang; Yuting Li (Arabian Journal of Geosciences, 2021)

Environmental Effects on the Spatiotemporal Variability of Fish Larvae in the Western Guangdong Waters, China - Yuting Feng; Lijun Yao; Hui Zhao; Jing Yu; Zhaojin Lin (Journal of Marine Science and Engineering, 2021)
Spawning grounds occupy an important position in the survival and reproduction of aquatic life, which plays an important role in the replenishment of fishery resources, especially in the China coasts where fishery resources are depleting. This study investigated environmental effects on the spatiotemporal variability of fish larvae in the western Guangdong waters (WGWs), on the basis of generalized additive models (GAMs) and center of gravity (CoG). Satellite data including sea surface salinity (SSS), sea surface temperature (SST), and in situ observations for fish larvae from April to June in 2014–2015 were used. Results showed that 40.3% of the total variation in fish larvae density was explained. SST, SSS, and depth showed positive effects in 23–24 °C and 27–30 °C, 24–32 PSU, and 0–60 m, and showed negative effects in 24–27 °C, 32–34.2 PSU, 60–80 m. Based on the stepwise GAMs, the most important factor was month, with a contribution of 10.6%, followed by longitude, offshore distance, depth, and latitude, with contributions of 7.0%, 7.0%, 6.3%, 4.2%, 3.9%, and 1.3%, respectively. Fish larvae CoG shifted northward by 0.6° N and eastwards by 0.13° E from April to June. The distribution of fish larvae in the WGWs was affected by complex submarine topography in the Qiongzhou Strait, coastal upwelling in the WGWs, and runoff from the Pearl River.

A self-attention capsule feature pyramid network for water body extraction from remote sensing imagery - Yongtao Yu; Yuting Yao; Haiyan Guan; Dilong Li; Zuojun Liu; Lanfang Wang; Changhui Yu; Shaozhang Xiao; Wenhao Wang; Lv Chang (International Journal of Remote Sensing, 2021)

Reduction of gut microbial diversity and short chain fatty acids in BALB/c mice exposure to microcystin-LR - Zhang Guilin; Zhang Pengyu; Li Wei; Hao Fengqi; Fangmei Chen; Yang Yu; Hou Yue; Tao Yuting (Ecotoxicology, 2020)

Effects of Fluorine on Intestinal Structural Integrity and Microbiota Composition of Common Carp - Huiyuan Yu; Yue Zhang; Peijun Zhang; Xinchi Shang; Yuting Lu; Yunhe Fu; Yuehong Li (Biological Trace Element Research, 2020)

Doxorubicin sensitizes cancer cells to Smac mimetic via synergistic activation of the CYLD/RIPK1/FADD/caspase-8-dependent apoptosis - Chengkui Yang; Qiao Ran; Yifei Zhou; Shan Liu; Cong Zhao; Xiaoliang Yu; Fang Zhu; Yuting Ji; Qian Du; Tao Yang; Wei Zhang; Sudan He (Apoptosis, 2020)

Exploration of the critical factors influencing the water quality in two contrasting climatic regions - Gelin Kang; Yu Qiu; Qingxiu Wang; Zuoda Qi; Yuting Sun; Yuqiu Wang (Environmental Science and Pollution Research, 2020)

Tumor-Targeted Chemoimmunotherapy with Immune-Checkpoint Blockade for Enhanced Anti-Melanoma Efficacy - Man Li; Yuting Yang; Chaoqun Xu; Jiaojie Wei; Yingke Liu; Xingli Cun; Qianwen Yu; Xian Tang; Sheng Yin; Zhirong Zhang; Qin He (The AAPS Journal, 2019)

CypD-mPTP axis regulates mitochondrial functions contributing to osteogenic dysfunction of MC3T3-E1 cells in inflammation - Xueqi Gan; Ling Zhang; Beilei Liu; Zhuoli Zhu; Yuting He; Junsheng Chen; Junfei Zhu; Haiyang Yu (Journal of Physiology and Biochemistry, 2018)

In Vitro-In Vivo Relationship of Amorphous Insoluble API (Progesterone) in PLGA Microspheres - Chenguang Pu; Qiao Wang; Hongjuan Zhang; Jingxin Gou; Yuting Guo; Xinyi Tan; Bin Xie; Na Yin; Haibing He; Yu Zhang; Yanjiao Wang; Tian Yin; et al. (Pharmaceutical Research, 2017)

Injectable Sustained-Release Depots of PLGA Microspheres for Insoluble Drugs Prepared by hot-Melt Extrusion - Yuting Guo; Yunning Yang; Luying He; Rong Sun; Chenguang Pu; Bin Xie; Haibing He; Yu Zhang; Tian Yin; Yanjiao Wang; Xing Tang (Pharmaceutical Research, 2017)

A Novel Non-specific Lipid Transfer Protein Gene from Sugarcane (NsLTPs), Obviously Responded to Abiotic Stresses and Signaling Molecules of SA and MeJA - Yun Chen; Jingjing Ma; Xu Zhang; Yuting Yang; Dinggang Zhou; Qing Yu; Youxiong Que; Liping Xu; Jinlong Guo (Sugar Tech, 2017)

Biodegradation of Endosulfan by Bacterial Strain Alcaligenes faecalis JBW4 in Argi-Udic Ferrosols and Hapli-Udic Isohumosols - Yu Zhang; Lusheng Zhu; Jinhua Wang; Jun Wang; Benying Su; Cheng Zhang; Yuting Shao; Chao Li (Water, Air, & Soil Pollution, 2016)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)

Hydrogeochemical Characterization of Groundwater in and Around a Wastewater Irrigated Forest in the Southeastern Edge of the Tengger Desert, Northwest China - Peiyue Li; Jianhua Wu; Hui Qian; Yuting Zhang; Nuan Yang; Lijun Jing; Peiyuan Yu (Exposure and Health, 2016)

Major Ion Chemistry and Quality Assessment of Groundwater in and Around a Mountainous Tourist Town of China - Peiyue Li; Yuting Zhang; Nuan Yang; Lijun Jing; Peiyuan Yu (Exposure and Health, 2016)

The spatial variation in forest burn severity in Heilongjiang Province, China - Yu Chang; Zhiliang Zhu; Yuting Feng; Yuehui Li; Rencang Bu; Yuanman Hu (Natural Hazards, 2016)

Arsenic speciation and kinetic release simulation of stream sediment contaminated by gold mining - Yongbing Cai; Yuting Mi; Jing Yu; Hua Zhang (Journal of Soils and Sediments, 2016)

Genes regulating lipid and protein metabolism are highly expressed in mammary gland of lactating dairy goats - Hengbo Shi; Jiangjiang Zhu; Jun Luo; Wenting Cao; Huaiping Shi; Dawei Yao; Jun Li; Yuting Sun; Huifen Xu; Kang Yu; Juan J. Loor (Functional & Integrative Genomics, 2015)

Association of Hematocrit and Pre-hypertension Among Chinese Adults: The CRC Study - Xuekui Liu; Jun Liang; Qinqin Qiu; Yan zhu; Yuting Sun; Pei Ying; Fei Teng; Yu Wang; Lu Qi (Cell Biochemistry and Biophysics, 2015)